Adhesive, adhesive tape, electrical product, vehicle-mounted component, and fixing method
By adjusting the monomer composition and structure of the polymer, the weight average molecular weight and crosslinking degree of the adhesive are improved, and the biocarbon content is increased. Combined with tackifier and crosslinking agent, the adhesive is solved at high and low temperatures. Performance problems, and the adhesive force to the bonded body with low polarity is improved, achieving environmentally friendly and efficient bonding effect.
Patent Information
- Application Number
- CN202411566191.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-24
- Filing Date
- 2020-12-16
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult for the existing adhesive to maintain strength at high temperatures and maintain good adhesion at low temperatures, especially when fixing the bonded body with low polarity. In addition, with the depletion of oil resources, there are environmental problems caused by the use of oil-derived materials.
By adjusting the monomer composition of the polymer, the weight average molecular weight and crosslinking degree of the polymer are increased by adjusting the monomer composition of the polymer, and the carbon content from the organism is increased, combining tackifier and crosslinking agent with a viscosity enhancer and a crosslinking agent. To improve the performance of the adhesive.
It realizes the strength at high temperature and good adhesion at low temperatures, while improving the adhesion to the bonded body with low polarity, and reducing petroleum resource consumption and environmental pollution by increasing the biological rate.
Smart Images

Figure CN119463752A_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of December 16, 2020, application number 202080087138.3, and invention name "Adhesives, tapes, electrical products, vehicle-mounted components and fixing methods". Technical Field
[0002] The present invention relates to an electrical product and a vehicle-mounted component having an adhesive, a tape, an adhesive sheet, an adhesive, a tape or an adhesive sheet, and a fixing method using the adhesive or the tape. Background Art
[0003] Adhesive tapes having an adhesive layer formed of an adhesive have been widely used to fix various parts on electrical products, vehicles, houses, building materials, etc. As adhesives, adhesives containing acrylic polymers having a structural unit derived from (meth)acrylates such as 2-ethylhexyl acrylate and n-butyl acrylate as a main component are known (for example, see Patent Documents 1 and 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-021067
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-120876 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In recent years, as the production bases of various companies have become globalized, assembly using adhesive tapes has gradually been carried out in a variety of environments. For example, even products that require performance in high-temperature environments, such as electrical products and automotive parts, are sometimes assembled in cold regions, requiring adhesives to have both high holding power at high temperatures and low-temperature adhesion that allows easy adhesion to the adherend even at low temperatures.
[0010] Low-temperature adhesion requires high fluidity in low-temperature environments, and in order to improve the retention at high temperatures, cohesion in high-temperature environments is required, but it is difficult for general adhesives to meet these two characteristics. In addition, since it is generally difficult for adhesives to improve the adhesion to adherends with low polarity, but automotive parts and electrical product parts often use resins with low polarity such as polyolefin resins represented by polypropylene resins, it is necessary to improve the adhesion to adherends with low polarity in these applications.
[0011] On the other hand, the exhaustion of petroleum resources and the emission of carbon dioxide caused by the combustion of petroleum products have been recognized as problems. Therefore, attempts have been made to save petroleum resources by using biomaterials instead of petroleum-derived materials, mainly in the medical field and packaging material field. Such attempts have spread to all fields, and the use of biomaterials has begun to be required in the fields of adhesives and tapes.
[0012] According to the research of the present inventors, it has been found that acrylic adhesives with structural units derived from conventionally commonly used n-butyl acrylate as the main component have good holding power at high temperatures, low temperature adhesion, and bonding properties to low-polarity adherends such as polyolefin resins. However, alkyl (meth)acrylates with a small number of carbon atoms such as n-butyl acrylate are produced from petroleum and cannot sufficiently increase the content of carbon derived from biomass (i.e., biomass ratio).
[0013] Therefore, an object of the present invention is to provide an adhesive and a tape which can improve the holding power at high temperature, the adhesion at low temperature, and the bonding property to a low-polarity adherend such as a polyolefin resin even if the biomass ratio is increased.
[0014] Means of solving problems
[0015] The inventors of the present invention have conducted intensive research and found that the above problems can be solved by setting the monomer components of the polymer used in the adhesive to predetermined components and setting the tan δ (23° C.) to a specific range, thereby completing the following present invention. That is, the gist of the present invention is the following [1] to
[32] .
[0016] [1] An adhesive comprising a polymer (X1) containing 48% by mass or more of a structural unit derived from a monomer (Y), wherein the monomer (Y) is at least one selected from a monomer (A1) represented by the following general formula (1) and a monomer (B1) represented by the following general formula (2),
[0017] When the storage modulus at 23°C is G'(23°C) and the loss modulus at 23°C is G"(23°C), tanδ(23°C) obtained by G"(23°C) / G'(23°C) is 0.8 to 1.3.
[0018]
[0019] In formula (1), R 1 Indicates H or CH3, R 2 Indicates -C n H 2n+1 , n represents an integer from 7 to 14,
[0020] In formula (2), R 3 Represents -C(=O)C mH 2m+1 , m represents an integer from 6 to 13.
[0021] [2] The adhesive according to [1] above, wherein the weight average molecular weight of the polymer (X1) is 200,000 to 1,000,000.
[0022] [3] The adhesive as described in [1] or [2] above, wherein the degree of crosslinking is 10 to 70%.
[0023] [4] The adhesive according to any one of [1] to [3] above, wherein, when the storage modulus at 0°C is G'(0°C), logG'(0°C) [Pa] is 5.0 to 6.5.
[0024] [5] The adhesive according to any one of [1] to [4] above, wherein, when the storage modulus at 23°C is G'(23°C), logG'(23°C)[Pa] is 4.8 to 5.5.
[0025] [6] The adhesive according to any one of [1] to [5] above, wherein, when the storage modulus at 80°C is G'(80°C), logG'(80°C) [Pa] is 4.1 to 4.8.
[0026] [7] The adhesive according to any one of [1] to [6] above, having a glass transition temperature (Tg) of 15°C or less.
[0027] [8] The adhesive according to any one of [1] to [7] above, wherein the biomass-derived carbon content is 40% by mass or more.
[0028] [9] The adhesive according to any one of [1] to [8], further comprising a tackifier.
[0029] 10]. An adhesive tape comprising an adhesive layer comprising the adhesive according to any one of [1] to [9].
[0030]
[11] The adhesive tape described in
[10] above further comprises a substrate, wherein the adhesive layer is provided on at least one surface of the substrate.
[0031]
[12] The adhesive tape as described in
[11] above, wherein the substrate is any one selected from a nonwoven fabric, a polyethylene terephthalate film and a foam.
[0032]
[13] A fixing method, using the adhesive described in any one of [1] to [9] or the tape described in any one of
[10] to
[12] to fix a component of an electrical product or a vehicle-mounted component.
[0033]
[14] . An adhesive sheet comprising the adhesive described in any one of [1] to [9] above,
[0034] The peak top molecular weight (Mtp) of the sol portion of the adhesive measured by gel permeation chromatography (GPC) is greater than or equal to 137,000 and less than or equal to 300,000,
[0035] The sol fraction (R sol ) is less than 90 mass %,
[0036] The adhesive has a glass transition temperature (Tg) of 5° C. or less.
[0037]
[15] The adhesive sheet as described in
[14] above, wherein the hardness (S) of the adhesive represented by the following general formula (3) is greater than or equal to 50,000 and less than or equal to 180,000,
[0038] S=Mw×R sol / D (3)
[0039] In formula (3), Mw represents the weight average molecular weight of the sol part of the adhesive measured by GPC, and R sol represents the sol fraction in the adhesive, and D represents the dispersion degree of the sol part of the adhesive measured by GPC.
[0040]
[16] The adhesive sheet according to
[14] or
[15] above, wherein the dispersion degree (D) of the sol part of the adhesive measured by GPC is 1.6 or more and less than 3.
[0041]
[17] . The adhesive sheet according to any one of
[14] to
[16] above, wherein the weight average molecular weight (Mw) of the sol portion of the adhesive measured by GPC is 190,000 or more and 700,000 or less.
[0042]
[18] The adhesive sheet according to any one of
[14] to
[17] , wherein the sol fraction (R sol ) is 45 mass % or more and 75 mass % or less.
[0043]
[19] . The adhesive sheet according to any one of
[14] to
[18] above, wherein the glass transition temperature (Tg) of the adhesive is 2.5°C or less.
[0044]
[20] . The adhesive sheet according to any one of
[14] to
[19] above, wherein the biomass ratio of the adhesive is 51% or more.
[0045]
[21] The adhesive sheet according to
[20] above, wherein the content of the structural unit derived from n-heptyl (meth)acrylate in the polymer (X1) is 48% by mass or more.
[0046]
[22] . An adhesive sheet comprising an adhesive containing a biological component,
[0047] The peak top molecular weight (Mtp) of the sol portion of the adhesive measured by gel permeation chromatography (GPC) is 137,000 or more and 300,000 or less,
[0048] The sol fraction (R sol ) is less than 90 mass %,
[0049] The adhesive has a glass transition temperature (Tg) of 5° C. or less.
[0050]
[23] The adhesive sheet as described in
[22] above, wherein the hardness (S) of the adhesive represented by the following general formula (3) is greater than or equal to 50,000 and less than or equal to 180,000,
[0051] S=Mw×R sol / D (3)
[0052] In formula (3), Mw represents the weight average molecular weight of the sol part of the adhesive measured by GPC, and R sol represents the sol fraction in the adhesive, and D represents the dispersion degree of the sol part of the adhesive measured by GPC.
[0053]
[24] The adhesive sheet according to
[22] or
[23] above, wherein the dispersion degree (D) of the sol part of the adhesive measured by GPC is 1.6 or more and less than 3.
[0054]
[25] The adhesive sheet according to any one of
[22] to
[23] above, wherein the weight average molecular weight (Mw) of the sol portion of the adhesive measured by GPC is 190,000 or more and 700,000 or less.
[0055]
[26] The adhesive sheet as described in any one of
[22] to
[25] above, wherein the sol fraction (R sol ) is 45 mass % or more and 75 mass % or less.
[0056]
[27] . The adhesive sheet according to any one of
[22] to
[26] above, wherein the glass transition temperature (Tg) of the adhesive is 2.5°C or less.
[0057]
[28] The adhesive sheet as described in any one of
[22] to
[27] above, wherein the biomass ratio of the adhesive is 51% or more.
[0058]
[29] The adhesive sheet according to any one of
[22] to
[28] , wherein the adhesive comprises a polymer (X2) containing 48% by mass or more of a structural unit derived from a monomer (Y2), wherein the monomer (Y2) is at least one selected from a monomer (A2) represented by the following general formula (4) and a monomer (B2) represented by the following general formula (5),
[0059]
[0060] In formula (4), R 4 Indicates H or CH3, R 5 Indicates -C n H 2n+1 , n represents an integer from 7 to 20,
[0061] In formula (5), R 6 Represents -C(=O)C m H 2m+1 , m represents an integer from 6 to 13.
[0062]
[30] The adhesive sheet according to
[29] above, wherein the content of the structural unit derived from n-heptyl (meth)acrylate in the polymer (X2) is 48% by mass or more.
[0063]
[31] . An electrical product comprising the adhesive described in any one of [1] to [9] above, the adhesive tape described in any one of
[10] to
[12] above, or the adhesive sheet described in any one of
[14] to
[30] above.
[0064]
[32] . A vehicle-mounted component comprising the adhesive described in any one of [1] to [9] above, the adhesive tape described in any one of
[10] to
[12] above, or the adhesive sheet described in any one of
[14] to
[30] above.
[0065] Effects of the Invention
[0066] The adhesive and adhesive sheet of the present invention improve the bioavailability and also improve the holding power at high temperatures, the adhesion at low temperatures, and the bonding properties to low-polarity adherends. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 Shows the outline of the cohesion test using the microshear displacement measurement test device and the enlarged view of part A. DETAILED DESCRIPTION
[0068] <First Invention>
[0069] Hereinafter, the first aspect of the present invention will be described in detail using embodiments.
[0070] <Adhesive>
[0071] [Polymer (X1)]
[0072] The adhesive of the present invention comprises a polymer (X1). The polymer (X1) comprises a structural unit derived from at least one monomer (Y1) selected from a monomer (A1) represented by the following general formula (1) and a monomer (B1) represented by the following general formula (2). In addition, in this specification, the term "monomer (Y1)" is also used to describe the monomer (A1) and the monomer (B1) together.
[0073]
[0074] In formula (1), R 1 Indicates H or CH3, R 2 Indicates -C n H 2n+1 , n represents an integer of 7 to 14, in formula (2), R 3 Represents -C(=O)C m H 2m+1 , m represents an integer from 6 to 13.
[0075] In the present invention, by including at least one of the structural units from monomer (A1) and monomer (B1), it is easy to adjust the tanδ (23°C) described below to an appropriate range, and it is also easy to improve the retention at high temperature, low temperature adhesion and bonding properties to low-polarity adherends. In addition, monomer (A1) and monomer (B1) are easy to produce from biological raw materials, and it is easy to improve the biological rate described below.
[0076] The polymer (X1) may contain structural units derived from one or both of the monomers (A1) and (B1), but preferably contains structural units derived from the monomer (A1). If the polymer (X1) contains structural units derived from the monomer (A1), it is easy to adjust tanδ (23°C) to a desired range, and it is also easy to improve the holding power at high temperatures, the low-temperature adhesion, and the bonding properties to low-polarity adherends.
[0077] In formula (1), R 2 The alkyl group (-C n H 2n+1 ) and R in formula (2) 3 The alkyl group (-C m H 2m+1 ) may be straight chain or branched, but a straight chain is more suitable from the viewpoint of making tanδ(23°C) within an appropriate range. 2 The n in formula (1) is preferably 7 to 10, more preferably 7. In addition, from the viewpoint of achieving good adhesion performance, it is preferred that R1 For H.
[0078] Therefore, the polymer (X1) preferably contains a compound derived from the general formula (1) wherein n is 7 to 10 and R 2 The structural unit of the linear monomer (A1) preferably contains a monomer derived from a monomer having n of 7 and R 2 The monomer (A1) is a linear structural unit. In this case, the monomer (A1) is more preferably R 1 For H.
[0079] Specific examples of the monomer (A1) include n-heptyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, n-decyl (meth)acrylate, 2-octyl (meth)acrylate, n-nonyl (meth)acrylate, undecyl (meth)acrylate, tetradecyl (meth)acrylate, myristyl (meth)acrylate, etc. These monomers (A1) may be used alone or in combination of two or more.
[0080] Specific examples of the monomer (B1) include vinyl decanoate, vinyl laurate, vinyl octanoate, vinyl nonanoate, etc. These monomers (B1) may be used alone or in combination of two or more.
[0081] Among the above-mentioned monomers (A1) and (B1), n-heptyl (meth)acrylate is preferred, and n-heptyl acrylate is more preferred. If n-heptyl (meth)acrylate is used, it is easy to improve the high temperature holding power, low temperature adhesion and bonding properties to low polarity adherends by setting tanδ (23°C) within an appropriate range.
[0082] Note that, in this specification, (meth)acrylate is used as a term representing one or both of acrylate and methacrylate, and the same applies to other similar terms.
[0083] In the above general formulas (1) and (2), R 2 and R 3 Preferably, carbon is derived from a biological source. 2 and R 3 If the carbon is derived from organisms, the biomass rate described below can be increased. 2 and R 3 The monomers (A1) and (B1) derived from biomass carbon can be obtained economically and easily by using saturated fatty acids or unsaturated fatty acids collected from animals and plants as raw materials and subjecting them to alcoholization and esterification.
[0084] In the present invention, the content of the structural unit derived from the monomer (Y1) (i.e., at least one monomer selected from the monomer (A1) and the monomer (B1)) in the polymer (X1) is 48% by mass or more. If the content is less than 48% by mass, it is difficult to adjust tanδ (23°C) to an appropriate range. In addition, it is difficult to improve the biomass rate while making the high temperature retention, low temperature adhesion and bonding properties to low polarity adherends all good.
[0085] From the viewpoint of adjusting tan δ (23° C.) to a desired range and improving the above-mentioned various properties while increasing the biomass rate, the content of the structural unit derived from the monomer (Y1) is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. In addition, for example, in order to include a predetermined amount of the functional group-containing monomer described later, the content of the structural unit derived from the monomer (Y1) is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97.5% by mass or less.
[0086] In addition, as described above, the monomer (A1) preferably contains n-heptyl (meth)acrylate. The content of the structural unit derived from n-heptyl (meth)acrylate in the polymer (X1) is preferably 48% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more, from the viewpoint of tanδ (23°C) and the viewpoint of improving the above-mentioned various properties while improving the biomass rate. In addition, the content of the structural unit derived from n-heptyl (meth)acrylate is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97.5% by mass or less.
[0087] Polymer (X1) preferably comprises the structural unit from other monomers except the above-mentioned monomer (A1), monomer (B1).Other monomers can be monomers with polymerizable carbon-carbon double bonds such as vinyl, (meth) acryloyl.As other monomers, preferably monomers containing polar groups (hereinafter also referred to as "polar group-containing monomer (C)").By polymer (X1) containing the structural unit from polar group-containing monomer (C), it is easy to improve the bonding force of adhesive, and it is also easy to improve the holding power under high temperature, low temperature adhesion and the bonding property for low polarity adherends, etc.
[0088] The polar group is a functional group having active hydrogen, and specifically includes a carboxyl group, a hydroxyl group, an amino group, an amide group, etc. The polar group may also be a functional group that can react with a crosslinking agent described later. The polar group-containing monomer (C) may be used alone or in combination of two or more.
[0089] As the polar group-containing monomer (C), any one of a carboxyl group-containing monomer (hereinafter also referred to as “carboxyl group-containing monomer (C1)”) and a hydroxyl group-containing monomer (hereinafter also referred to as “hydroxyl group-containing monomer (C2)”) is preferred, and a combination of these is more preferred.
[0090] Examples of the carboxyl group-containing monomer (C1) include acrylic acid, methacrylic acid, crotonic acid, etc. Among these, at least one selected from acrylic acid and methacrylic acid is preferred, and acrylic acid is more preferred.
[0091] The content of the structural unit from carboxyl group-containing monomer (C1) in polymer (X1) is preferably 0.5~10 mass %.By making the content of the structural unit from (C1) in the above range, the bonding force of adhesive is appropriately improved, thereby easily improving the holding power, low temperature adhesion and bonding property relative to low polarity adherend under high temperature.From these viewpoints, the content of the structural unit from carboxyl group-containing monomer (C1) is more preferably 1~8 mass %, and further more preferably 2~6 mass %.
[0092] Examples of the hydroxyl group-containing monomer (C2) include (meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, and allyl alcohol. Among these, (meth)acrylates having a hydroxyl group are preferred, and 2-hydroxyethyl (meth)acrylate is more preferred.
[0093] From the viewpoint of improving various properties of the adhesive, the content of the structural unit derived from the hydroxyl-containing monomer (C2) in the polymer (X1) is preferably 0.1 to 15% by mass, more preferably 0.05 to 10% by mass, and more preferably 0.1 to 5% by mass. In addition, the hydroxyl-containing monomer (C2) is preferably used in combination with the carboxyl-containing monomer (C1), and the content of the structural unit derived from the hydroxyl-containing monomer (C2) when used in combination is preferably 0.01 to 5% by mass, more preferably 0.05 to 2% by mass, and more preferably 0.1 to 0.9% by mass. When used in combination with the carboxyl-containing monomer (C1), even such a small amount can improve the adhesive force of the adhesive, so that the holding power at high temperature, low temperature adhesion and bonding property to low-polarity adherends are easily improved.
[0094] Examples of the amide group-containing monomer include isopropyl (meth)acrylamide and dimethylaminopropyl (meth)acrylamide.
[0095] As other monomers other than monomers (A1) and (B1), other monomers other than monomers containing functional groups can be used, and other alkyl (meth)acrylates other than the compound represented by general formula (1) can be mentioned. Examples of such alkyl (meth)acrylates include alkyl (meth)acrylates having an alkyl group with 1 to 6 carbon atoms such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, and n-hexyl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, an ester formed from 5,7,7-trimethyl-2-(1,3,3-trimethylbutyl)octanol-1 and (meth)acrylic acid, behenyl (meth)acrylate, and eicosyl (meth)acrylate.
[0096] In addition, examples of other monomers include (meth)acrylates having an alicyclic structure such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate, (meth)acrylates having an aromatic ring such as benzyl (meth)acrylate and 2-phenoxyethyl (meth)acrylate, monomers having an epoxy group such as glycidyl (meth)acrylate, monomers having a nitrile group such as (meth)acrylonitrile, 2-butylethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, styrene, and the like.
[0097] Monomers other than the polar group-containing monomer may be used alone or in combination of two or more.
[0098] The above-mentioned other monomers preferably contain biomass-derived carbon from the viewpoint of improving the biomass ratio described later, but may contain no biomass-derived carbon but may contain petroleum-derived monomers.
[0099] The weight average molecular weight (Mw) of the polymer (X1) is preferably 200,000 to 1,000,000.
[0100] If the weight average molecular weight (Mw) is 200,000 or more, the shear strength of the adhesive can be increased, and the holding power of the adhesive at high temperatures can be improved. In addition, if it is 1,000,000 or less, the adhesive strength of the adhesive is good, and it is easy to improve low-temperature adhesion, bonding properties to low-polarity adherends, etc.
[0101] From these viewpoints, the weight average molecular weight (Mw) is more preferably 300,000 or more, more preferably 400,000 or more, more preferably 900,000 or less, and even more preferably 800,000 or less.
[0102] The weight average molecular weight can be appropriately adjusted by appropriately selecting the amount of the polymerization initiator used, polymerization conditions such as the polymerization temperature, the polymerization method, and the like.
[0103] In addition, the weight average molecular weight is a weight average molecular weight converted into standard polystyrene measured by gel permeation chromatography (GPC).
[0104] The polymer (X1) is a main component in the adhesive. In order to impart appropriate adhesiveness, the content of the polymer (X1) in the adhesive is, for example, 50% by mass or more, preferably 60% by mass or more, and more preferably 65% by mass or more. In addition, in order to be able to mix a predetermined amount of components other than the polymer (X1) such as a tackifier and a cross-linking agent in the adhesive, the polymer (X1) in the adhesive is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less.
[0105] (Method for producing polymer (X1))
[0106] The polymer (X1) can be obtained by subjecting a mixture of the above-mentioned raw material monomers to a radical reaction in the presence of a polymerization initiator.
[0107] There is no particular limitation on the method of free radical reaction, and examples thereof include living radical polymerization, free radical polymerization, etc. By living radical polymerization, a copolymer with a more uniform molecular weight and composition can be obtained compared with free radical polymerization, the generation of low molecular weight components, etc. can be suppressed, and the cohesive force of the above-mentioned adhesive becomes higher. There is no particular limitation on the polymerization method, and a conventionally known method can be used. For example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. can be mentioned. Among them, solution polymerization is preferred because the synthesis is simple.
[0108] When solution polymerization is used as the polymerization method, examples of the reaction solvent include ethyl acetate, toluene, methyl ethyl ketone, dimethyl sulfoxide, ethanol, acetone, diethyl ether, etc. These reaction solvents may be used alone or in combination of two or more.
[0109] The polymerization initiator is not particularly limited, and examples thereof include organic peroxides and azo compounds. Examples of the organic peroxide include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxy pivalate, tert-butyl peroxy pivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy isobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and tert-butyl peroxy laurate. Examples of the azo compound include azobisisobutyronitrile and azobiscyclohexanecarbonitrile. These polymerization initiators may be used alone or in combination of two or more.
[0110] In the case of living radical polymerization, as the above-mentioned polymerization initiator, for example, an organic tellurium polymerization initiator can be cited. The above-mentioned organic tellurium polymerization initiator is not particularly limited as long as it is generally used for living radical polymerization, and for example, an organic tellurium compound (teruler compound), an organic dialkyl tellurium compound (terulid compound), etc. can be cited. In addition, in the living radical polymerization, in addition to the above-mentioned organic tellurium polymerization initiator, an azo compound can also be used as the above-mentioned polymerization initiator for the purpose of accelerating the polymerization rate.
[0111] [Thickener]
[0112] The adhesive of the present invention preferably also comprises a tackifier in addition to the above-mentioned polymer (X1). By containing a tackifier, the viscosity of the adhesive is improved. In addition, the bonding property of low-polarity adherends, etc. is also easily improved. And then, for example, by containing a tackifier in a manner such that the glass transition temperature (Tg) is below the upper limit value described later, it is possible to make the low-temperature adhesion good.
[0113] Examples of the tackifier include rosin ester resins such as rosin resins, polymerized rosin ester resins, rosin tackifiers such as hydrogenated rosin resins, terpene resins, terpene phenol resins, terpene tackifiers such as coumarone indene resins, alicyclic saturated hydrocarbon resins, C5 petroleum resins, C9 petroleum resins, C5-C9 copolymerized petroleum resins, etc. These tackifier resins may be used alone or in combination of two or more.
[0114] Among the above, rosin-based tackifiers and terpene-based tackifiers are preferred. These tackifiers can be easily synthesized from biological raw materials, thereby more easily improving the biomass rate. For example, rosin-based tackifiers are derived from natural resins such as pine oil, and terpene-based tackifiers are derived from essential oils of plants, etc. In addition, as tackifiers, rosin-based tackifiers are particularly suitable. By using rosin-based tackifiers, it is possible to have more excellent bonding properties relative to low-polarity adherends such as polyolefin resins represented by polypropylene resins.
[0115] The softening temperature of the tackifier is preferably 120°C or higher. The polymer (X1) has a tendency to have a lower glass transition temperature, and the holding power at high temperature is easily reduced. However, by using it in combination with a tackifier having a relatively high softening temperature, the holding power at high temperature can be prevented from being reduced. From such a viewpoint, the softening temperature of the tackifier is further preferably 130°C or higher, and more preferably 140°C or higher. In addition, from the viewpoint of imparting appropriate adhesive properties to the adhesive, the softening temperature of the tackifier is preferably 165°C or lower, further preferably 160°C or lower, and more preferably 155°C or lower. In addition, the softening temperature can be measured in accordance with JIS K2207.
[0116] When the adhesive contains a tackifier, the content of the tackifier is not particularly limited, but is preferably 10 to 50 parts by mass relative to 100 parts by mass of the polymer (X1). If the content of the tackifier is above the above lower limit, it is easy to make the low-temperature adhesion and the bonding properties relative to the low-polarity adherend good. In addition, by being below the above upper limit, it is possible to prevent the retention force at high temperatures from being reduced. From the above viewpoints, the content of the tackifier is further preferably 12 to 40 parts by mass, more preferably 15 to 35 parts by mass, and particularly preferably 18 to 30 parts by mass.
[0117] [Crosslinking agent]
[0118] The adhesive of the present invention is preferably cross-linked by mixing with a cross-linking agent. That is, the adhesive is preferably cross-linked by an adhesive composition containing a cross-linking agent in addition to the above-mentioned polymer (X1) or the polymer (X1) and the thickener. The cross-linking agent can, for example, react with the polar group of the polymer (X1) to cross-link the adhesive.
[0119] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, metal chelate crosslinking agents, etc. Among these, at least one selected from isocyanate crosslinking agents and epoxy crosslinking agents is most preferred, and isocyanate crosslinking agents are more preferred.
[0120] The isocyanate crosslinking agent is not particularly limited as long as it is a compound having two or more isocyanate groups in one molecule, and examples thereof include toluene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, 1,5-naphthalene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, xylene diisocyanate, toluene diisocyanate adducts of trimethylolpropane, etc. Among these, toluene diisocyanate and toluene diisocyanate adducts of trimethylolpropane are preferred.
[0121] Examples of commercially available isocyanate crosslinking agents include various polyisocyanate compounds such as Coronet L-45E and Coronet L-55E (manufactured by Tosoh Corporation), biuret polyisocyanate compounds such as Sumijule N (manufactured by Sumitomo Bayer Polyurethanes), Desmodur IL and Desmodur HL (manufactured by Bayer AG), and Polyisocyanate compounds having an isocyanurate ring such as El AG (manufactured by Nippon Polyurethane Co., Ltd.), Coronet EH (manufactured by Nippon Polyurethane Co., Ltd.), and adduct polyisocyanate compounds such as Smijule L (manufactured by Sumitomo Bayer Polyurethane Co., Ltd.), Coronet L, and Coronet HL (manufactured by Nippon Polyurethane Co., Ltd.).
[0122] The epoxy crosslinking agent is not particularly limited as long as it is a compound having two or more epoxy groups in one molecule, and examples thereof include diglycidyl aniline, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane triglycidyl ether, 1,3-bis(N,N-diglycidylaminoethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.
[0123] As commercially available items of the epoxy-based crosslinking agent, for example, E-AX and E-5C (produced by Soken Chemical Co., Ltd.) may be mentioned.
[0124] The cross-linking agent may be used alone or in combination of two or more.
[0125] The amount of the crosslinking agent in the adhesive may be appropriately changed depending on the type of polymer (X1), desired physical properties such as the degree of crosslinking, etc., but is, for example, 0.1 to 20 parts by mass, preferably 0.4 to 8 parts by mass, more preferably 0.7 to 4 parts by mass, relative to 100 parts by mass of the polymer (X1).
[0126] (Degree of cross-linking)
[0127] The degree of crosslinking of the adhesive of the present invention is preferably 10 to 70%. By setting the degree of crosslinking within the above range, it is easy to improve the holding power at high temperature, low temperature adhesion, bonding properties relative to low-polarity adherends, etc. From such a viewpoint, the degree of crosslinking of the adhesive is preferably 20% or more, more preferably 30% or more, more preferably 60% or less, and even more preferably 50% or less. The degree of crosslinking of the adhesive is represented by the gel fraction, and the measurement method thereof is shown in the examples. The degree of crosslinking of the adhesive can be appropriately adjusted by changing the amount of the crosslinking agent, etc.
[0128] [Other additives]
[0129] The adhesive of the present invention may contain additives such as silane coupling agents, antioxidants, UV protection agents, plasticizers, emulsifiers, softeners, fillers, pigments, dyes, etc. as needed. Even these additives are preferably selected from materials derived from organisms within the possible range from the viewpoint of improving the bioavailability.
[0130] <Storage modulus>
[0131] (tanδ(23℃))
[0132] The adhesive of the present invention has a tanδ(23°C) expressed as G'(23°C) / G'(23°C) of 0.8 to 1.3, assuming that the storage modulus at 23°C is G'(23°C) and the loss modulus at 23°C is G"(23°C). When tanδ(23°C) is less than 0.8 or exceeds 1.3, it is difficult to satisfy all properties such as high temperature holding power, low temperature adhesion, and bonding properties to low-polarity adherends such as polyolefin resins. From these viewpoints, tanδ(23°C) is preferably 0.85 or more, more preferably 0.88 or more, and is preferably 1.2 or less, more preferably 1.1 or less, and even more preferably 1.0 or less.
[0133] Tan δ (23°C) can be adjusted by the type and amount of the monomer components used in the polymer (X1), for example, by changing the R 2 , R 3 When the polymer (X1) is made straight chain or the values of n and m are made small, tanδ(23°C) tends to be large. In addition, by adjusting the combination of the tackifier resin and the monomer so that the glass transition temperature (Tg) is within the range of -255 to 15°C, tanδ(23°C) can be easily adjusted to the desired range. In addition, it can also be adjusted according to the molecular weight of the polymer (X1). For example, if the molecular weight of the polymer (X1) is made small, the value of tanδ(23°C) tends to be small.
[0134] (Storage modulus at 23°C)
[0135] If the storage modulus at 23°C is G'(23°C), logG'(23°C)[Pa] is preferably 4.8 to 5.5. By setting logG'(23°C)[Pa] within the above range, it is easy to improve the adhesion characteristics at room temperature, for example, it is easy to improve the bonding properties to low-polarity adherends at room temperature. From this point of view, logG'(23°C)[Pa] is more preferably 4.85 to 5.4, and even more preferably 4.9 to 5.3.
[0136] (Storage modulus at 80°C)
[0137] If the storage modulus at 80°C is G'(80°C), logG'(80°C)[Pa] is preferably 4.1 to 4.8. By setting logG'(80°C)[Pa] within the above range, the cohesive force at high temperature can be improved, and the adhesiveness and holding power at high temperature can be improved. From this point of view, logG'(80°C)[Pa] is more preferably 4.15 to 4.75, and even more preferably 4.2 to 4.7.
[0138] (Storage modulus at 0°C)
[0139] If the storage modulus at 0°C is G'(0°C), logG'(0°C)[Pa] is preferably 5.0 to 6.5. By setting logG'(0°C)[Pa] within the above range, low-temperature adhesion can be improved. From this viewpoint, logG'(0°C)[Pa] is more preferably 5.4 to 6.4, and even more preferably 5.5 to 6.3.
[0140] In addition, logG'(0°C)[Pa] represents the logarithm of the storage modulus expressed in "Pa". Other similar descriptions are also synonymous.
[0141] The storage modulus G' at 0°C, 23°C and 80°C can be adjusted according to the type and amount of the monomer components used in the polymer (X1). For example, by setting the type and content of the monomer (A1) and the monomer (B1) according to the above description, it is easy to adjust to the above range. In addition, the storage modulus G' at each temperature can also be adjusted according to the weight-average molecular weight and the degree of crosslinking. For example, if the weight-average molecular weight and the degree of crosslinking are high, the storage modulus G' at each temperature tends to be higher. In addition, it can also be adjusted by molecular weight distribution. For example, the storage modulus G' increases as the molecular weight distribution narrows, and tends to decrease as the molecular weight distribution broadens.
[0142] (Glass transition temperature (Tg))
[0143] The glass transition temperature (Tg) of the adhesive of the present invention is preferably 15°C or less. By setting it to 15°C or less, tanδ (23°C) tends to become larger, and the holding power at high temperature, low temperature adhesion, etc. tend to become good. From these viewpoints, the glass transition temperature (Tg) is preferably 10°C or less, and more preferably 5°C or less. Although the glass transition temperature (Tg) of the adhesive is not particularly limited, from the viewpoint of improving the holding power at high temperature, it is, for example, -40°C or more, preferably -28°C or more, more preferably -25°C or more, and even more preferably -20°C or more.
[0144] The glass transition temperature (Tg) can be adjusted according to the type and amount of the monomers constituting the polymer (X1). In addition, it can also be adjusted by the type and amount of the tackifier, for example, by using a substance with a high softening temperature as the tackifier, or by increasing the amount of the tackifier, the glass transition temperature (Tg) can be easily increased. The glass transition temperature (Tg) can also be adjusted by adding microparticles, etc.
[0145] The storage modulus G' and loss modulus G" at the above-mentioned temperatures are values obtained by measuring under the measuring conditions described in the examples described below using a polymer dynamic viscoelasticity measuring apparatus. tanδ(23°C) is a value calculated based on the storage modulus G'(23°C) and loss modulus G"(23°C) measured at 23°C. In addition, the glass transition temperature (Tg) is measured under the measuring conditions described in the examples described below using a polymer dynamic viscoelasticity measuring apparatus.
[0146] (Biological rate)
[0147] The adhesive of the present invention preferably has a biomass carbon content (hereinafter also referred to as "biomass rate") of 40% by mass or more. Generally speaking, a biomass rate of 40% by mass or more is the benchmark for "biomass products". Biomass products can save petroleum resources by using renewable organic resources, and can also reduce carbon dioxide emissions generated by the combustion of petroleum products, thereby reducing the load on the environment. From these viewpoints, the biomass rate is more preferably 50% by mass or more, and even more preferably 60% by mass or more. In addition, the higher the biomass rate, the better, as long as it is below 100% by mass.
[0148] Carbon from organisms contains a certain proportion of radioactive isotopes (C-14), while carbon from petroleum contains almost no C-14. Therefore, the biomass ratio can be calculated by measuring the concentration of C-14 contained in the adhesive or the tape described later. Specifically, it can be measured based on ASTM D6866, a standard used in many bioplastic industries.
[0149] (Viscosity value)
[0150] The adhesive of the present invention preferably has a tape peeling limit value of 400 gf·s or more at 23° C. as measured by a tack test. The tack test is performed as follows.
[0151] First, place the tape on a plate set at 23°C in a viscosity tester (e.g., TAC-1000 produced by Reska Corporation) with the adhesive layer facing upward. Note that the non-measurement surface of the tape is backed by a film such as a polyethylene terephthalate (PET) film. Then, press a cylindrical stainless steel probe with a diameter of 5 mm on the tape at a detection temperature of 23°C, a pressing speed of 2mm / s, and a pressing load of 100gf, and keep it in this state for 0.1 seconds. After that, lift the probe at an increase speed of 0.2mm / s. Measure the force applied to the tape during this period.
[0152] In the above, an example in which the adhesive forms a tape has been described. However, even when the adhesive does not form a tape, the same measurement can be performed by placing the adhesive on a plate set at 23° C. in a tack tester.
[0153] The above-mentioned peeling limit value refers to the integral value from time T1 when the force is displayed as 0 to the time when the maximum force (peak value) is displayed in the force-time curve representing the force applied to the tape at 23°C measured by the above-mentioned adhesion test. In the adhesion test, when the probe is pressed against the tape, the force-time curve decreases, and then when the probe begins to be lifted, the force-time curve gradually increases. The integral value from time T1 when the force is displayed as 0 to time T2 when the maximum force (peak value) is calculated and used as the peeling limit value.
[0154] By adjusting the peeling limit value to the above range, even in the case of high temperature and high humidity and when resilience is required, the peeling of the tape can be suppressed. The preferred lower limit of the peeling limit value is 450 gf·s, and the more preferred lower limit is 500 gf·s. In addition, the upper limit of the peeling limit value is not particularly limited.
[0155] (Adhesive Preparation)
[0156] The adhesive of the present invention can be formed by preparing an adhesive composition, for example. The adhesive composition is composed of components for forming an adhesive, specifically, in addition to the polymer (X1), it also includes a tackifier, a cross-linking agent, and other additives as required. The adhesive composition can also be diluted by a diluent solution such as an organic solvent. The diluent solution can be a solvent used when synthesizing the polymer (X1), or it can be added after the polymer (X1) is synthesized.
[0157] The adhesive composition can be cross-linked by heating and drying as needed to become an adhesive. The adhesive is generally used in adhesive tapes and the like and can constitute an adhesive layer.
[0158] <Tape>
[0159] The adhesive tape of the present invention is an adhesive tape comprising an adhesive layer formed by the above-mentioned adhesive. The adhesive tape may be a non-supported adhesive tape without a substrate or a tape having a substrate, but preferably a tape having a substrate. In addition, the adhesive tape may be an adhesive sheet as described later.
[0160] A non-supported tape is a double-sided tape used without a substrate and with a single adhesive layer. A tape with a substrate includes a substrate and an adhesive layer disposed on at least one surface of the substrate. In this case, the tape may be provided with adhesive layers on both sides of the substrate and used as a double-sided tape, or may be provided with an adhesive layer only on one side of the substrate and used as a single-sided tape. For each type of tape, a release sheet may be appropriately attached to the surface of the exposed adhesive layer for protection. The release sheet is a material in which a release agent is coated on at least one side of the release sheet substrate to form a release surface, and may be attached in a manner that the release surface is in contact with the adhesive layer.
[0161] In the double-sided tape having adhesive layers on both sides of a substrate, at least one adhesive layer may be composed of the adhesive of the present invention.
[0162] [Base material]
[0163] The substrate used for the adhesive tape is not particularly limited, but is preferably a resin film, a nonwoven fabric, or a foam.
[0164] As the resin component constituting the resin film, specifically, there can be listed polyesters (PES) such as polyethylene terephthalate (PET), polyethylene furandicarboxylate (PEF), polylactic acid (PLA), polypropylene terephthalate (PTT), polybutylene succinate (PBS), polyethylene (PE), polypropylene (PP), ethylene vinyl acetate copolymer (EVA) and other polyolefins, polyurethane (PU), triacetyl cellulose (TAC), polyamide (PA), etc. These resin components can be used alone or in combination of two or more. As the resin film, polyethylene terephthalate film (PET film) is preferred among the above. The mechanical strength of the PET film is good and can properly support the adhesive layer. In addition, PET films are commercially available as products with high biomass rate, which can also easily increase the biomass rate of the tape.
[0165] The nonwoven fabric may be a nonwoven fabric made of a resin component or a nonwoven fabric using fibers other than resin components such as pulp. The nonwoven fabric using fibers other than resin components may be formed by fibers other than resin components alone or by both fibers other than resin components and resin fibers. As the resin component, for example, a suitable selection may be made from the materials listed as the resin components constituting the above-mentioned resin film. In addition, nonwoven fabrics using pulp can be purchased commercially as products with a high biomass rate, and the biomass rate of the adhesive tape can also be easily increased.
[0166] When a foam is used as the substrate, examples of the foam include polyolefin resin foams using polyolefin resins such as PE, PP, and EVA as a resin component, and polyurethane foams using polyurethane resins as a resin component.
[0167] The resin component constituting the resin film, nonwoven fabric and foam may be any one of a petroleum-derived resin, an animal-derived resin, or a petroleum-derived resin and a plant-derived resin. However, in order to make the adhesive tape a biomass product, it is preferred that at least an animal-derived resin be included. For example, when the substrate is a PET film, PET derived from animals and plants may be used. In addition, when a polyolefin resin foam is used as the substrate, an animal-derived resin may be used as the polyolefin resin constituting the foam.
[0168] The thickness of the substrate is not particularly limited for each type of adhesive tape, and may be, for example, 1 to 2000 μm. In addition, the preferred range of the thickness of the substrate varies depending on the type of substrate used, and for example, when the substrate is a resin film or a nonwoven fabric, it is preferably 1 to 100 μm, and more preferably 5 to 50 μm. By making the thickness of these substrates 5 to 100 μm, a certain mechanical strength can be given to the adhesive tape without damaging the flexibility.
[0169] If the substrate is a foam, the thickness of the substrate is preferably 50 to 2000 μm. Within the above range, the substrate can exhibit high impact resistance and high flexibility to closely adhere to the shape of the adherend.
[0170] In each adhesive tape, the thickness of the adhesive layer is not particularly limited, and may be, for example, about 5 to 200 μm, preferably 10 to 100 μm. If the thickness of the adhesive layer is within this range, the obtained adhesive tape can exert sufficient adhesive strength.
[0171] The total thickness of the adhesive tape (the sum of the thickness of the substrate and the adhesive layer) is preferably 10 to 400 μm. When the total thickness of the adhesive tape is within this range, the obtained adhesive tape can exhibit sufficient adhesive strength.
[0172] (Cohesion)
[0173] The adhesive tape of the present invention preferably has an offset at 23°C of 500 μm or less, more preferably 400 μm or less, further preferably 300 μm or less, and particularly preferably 250 μm or less, as measured by a cohesion test. In addition, the adhesive of the present invention preferably has an offset at 80°C of 1200 μm or less, more preferably 1000 μm or less, and further preferably 800 μm or less, as measured by a cohesion test. If the offset at 23°C and 80°C decreases as described above, the cohesion of the adhesive layer increases, and the retention at room temperature and high temperature increases.
[0174] The above-mentioned displacement is the displacement generated when a predetermined load is applied in the shear direction for 3 minutes, and the detailed measurement method will be described later.
[0175] In addition, the ratio of the offset amount (offset amount after load removal) when the load is removed after the load is applied in the shear direction for 3 minutes to the offset amount (offset amount before load removal) is defined as the offset displacement recovery rate (%). The offset displacement recovery rate (%) is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less, and is preferably 5% or more, more preferably 10% or more, and even more preferably 15% or more. When the recovery rate reaches the above range, the followability to the adherend becomes better when the tape is pressed, and the adhesiveness and adhesive force are improved.
[0176] The offset can be obtained by using Figure 1 The cohesion force was measured by using the micro-shear displacement measurement tester (manufactured by Asahi Seiko Co., Ltd., shear creep measurement device, NST1).
[0177] First, peel off the release sheet on one side of the double-sided tape to be tested, and stick a corona-treated polyethylene terephthalate (PET) film on the surface of one exposed adhesive layer of the double-sided tape. Then, cut it into 1 cm wide x 12 cm long to make a test piece 5. Set the thermostat 4 of the device to 23°C or 80°C and leave it until it stabilizes at the set temperature. The thermostat 4 may also be a combination of two or more thermostats as appropriate.
[0178] The other release sheet of the test piece 5 was peeled off and removed about 3 cm from the end thereof, and the exposed adhesive layer was attached to the adherend 3 with an adhesive area of 5 mm × 20 mm. At this time, the portion of the release sheet 8 other than the end was attached to the adhesive layer 7. The surface of the other exposed adhesive layer 7 of the test piece 5 was attached to the adherend 3 with an adhesive area of 5 mm × 20 mm. The adherend 3 was made of SUS.
[0179] A quartz block 2 (quartz glass plated with chrome) with a mirror-finished end face is placed on the attachment surface. The mirror-finished end face 10 of the block 2 is irradiated with laser light from a laser interferometer 1 (for example, "SI-F1" manufactured by Keyence).
[0180] The test piece 5 is mounted on a line connected to a 200g weight 6 and left at a constant temperature for 5 minutes. After 5 minutes, in addition to the load of the weight 6 applied to the test piece 5, a horizontal shear load is also applied to the test piece 5. After 3 minutes of applying the load, the displacement of the block 2 on the test piece 5 is detected by the laser interferometer 1, and the detected value is used as the offset of the adhesive.
[0181] In addition, as described above, the load is applied, and the load is removed after 3 minutes, and the offset (after the load is removed) after 3 minutes after the load is removed is measured, and the offset measured before the load is removed as described above is taken as the offset (before the load is removed), and the offset (after the load is removed) / offset (before the load is removed) × 100% (%) is taken as the offset displacement recovery rate (%). In addition, the offset (after the load is removed) is measured by the laser interferometer 1 in the same manner as the offset (before the load is removed). The specific calculation method of the offset displacement recovery rate (%) is as follows.
[0182] Deflection displacement recovery rate (%) = (deflection displacement after load removal for 3 minutes (μm) / (deflection displacement after load application for 3 minutes (μm)) × 100
[0183] The above description shows the method for measuring the offset of the double-sided tape. For the single-sided tape, except for omitting the PET film on one adhesive layer surface, it can be similarly performed. In addition, for the double-sided tape, the same measurement can be performed for the non-supported tape without a substrate. In addition, for the double-sided tape, when the release sheet is not attached to the adhesive layer, the process of peeling it can be omitted, and the rest is performed in the same way.
[0184] (Biological rate of tape)
[0185] The adhesive tape of the present invention, based on the same viewpoint as the above-mentioned adhesive, preferably has a biomass ratio of 40% by mass or more, further preferably 50% by mass or more, and more preferably 60% by mass or more. In addition, the higher the biomass ratio, the better, as long as it is below 100% by mass. Note that the biomass ratio of the adhesive tape usually varies depending on the components (for example, the adhesive layer and the substrate). Therefore, the biomass ratio can be calculated by finding the biomass ratio of each component and taking the weighted average of the masses of each component as weights.
[0186] (Manufacturing method of adhesive tape)
[0187] The manufacture method of adhesive tape is not particularly limited, and can be manufactured by the manufacture method known in the past. For example, first, prepare the adhesive composition diluted with organic solvent etc. as required, apply the adhesive composition on the support such as release sheet, heat and dry as required, form adhesive layer. When applying adhesive composition on release sheet, it can be applied on the release surface of release sheet. The adhesive layer formed on the support such as release sheet and then fits with base material, and obtains the adhesive tape with base material. In addition, adhesive composition can also be directly applied on base material, heat and dry as required, thereby obtain the adhesive tape that adhesive layer is provided on base material.
[0188] When producing a double-sided tape, the adhesive layer may be formed on both sides of the substrate by any of the above methods.
[0189] In addition, in the case of manufacturing an unsupported adhesive tape, the adhesive composition can be applied to a release sheet, heated and dried as required, and an adhesive layer can be formed to obtain the adhesive. In this case, the release sheet can be further laminated to the formed adhesive layer to protect the adhesive layer. In the case of an unsupported adhesive tape, the adhesive layer can be peeled off from the release sheet and used.
[0190] (Application of adhesive)
[0191] The use of the adhesive and tape of the present invention is not particularly limited, but is preferably used in electrical products and vehicle applications. For example, in electrical products, it is preferably used to fix the parts that constitute the electrical products. Specifically, in electrical products, the parts can be fixed to each other by an adhesive or tape. Therefore, the present invention also provides an electrical product comprising the above-mentioned adhesive or tape. As electrical products, there is no particular limitation, and portable electronic devices, various displays such as televisions, washing machines, refrigerators, dishwashing machines, vacuum cleaners, printers, various audio equipment, etc. can be listed.
[0192] In addition, in vehicle applications, it is preferably used, for example, to fix vehicle-mounted components. As vehicle-mounted components, vehicle interior materials can be listed, for example, vehicle-mounted panels such as ceiling panels, door panels, and instrument panels, automobile air conditioners, door trims, damping parts, badges, decorative films, waterproof parts, etc. The vehicle-mounted components can be fixed to the vehicle, for example, by an adhesive or tape. Therefore, the present invention also provides a vehicle-mounted component having the above-mentioned adhesive or tape.
[0193] Although electrical products and vehicle interiors are sometimes exposed to high temperatures, the adhesive of the present invention can also exert high holding power in high temperature environments, so that the parts of electrical products and vehicle-mounted components can be stably fixed. On the other hand, the assembly of electrical products and vehicles is sometimes carried out in cold areas, but even in cold areas, the adhesive or tape can be easily pasted on the parts of electrical products or vehicle-mounted components, so the assembly is good. In addition, the parts of electrical products or vehicle-mounted components can be low-polarity composed of polyolefin resins represented by polypropylene resins, but even if these are low-polarity, as long as the adhesive or tape of the present invention is used, they can be bonded with high adhesion.
[0194] <Second Invention>
[0195] Hereinafter, the second invention of the present invention will be described in detail using embodiments.
[0196] [Adhesive sheet]
[0197] The adhesive sheet of the present invention has an adhesive containing a component from a plant (a component from a plant). For example, the polymer (X2) contained in the adhesive as described later may contain a monomer component from a plant as a structural unit. In addition, components other than the polymer (X2) such as a tackifier may also contain a component from a plant. If there is no adhesive containing a component from a plant, it is difficult to improve the biomass rate of the adhesive sheet.
[0198] (Adhesive)
[0199] The peak molecular weight (Mtp) of the gel permeation chromatography (GPC) of the sol part of the adhesive in the adhesive sheet of the present invention is 137,000 or more and 300,000 or less, the sol fraction (Rsol) of the adhesive is 90% by mass or less, and the glass transition temperature (Tg) of the adhesive is 5° C. or less. Thus, the biomass rate of the adhesive sheet can be improved, the low-temperature adhesiveness can be improved, and the retention force at high temperature and the bonding property to the low-polarity adherend can be improved.
[0200] <Peak top molecular weight of sol part (Mtp)>
[0201] The peak molecular weight (Mtp) of the GPC of the sol part of the adhesive in the adhesive sheet of the present invention is more than 137000 and less than 300000. If the above-mentioned peak molecular weight is less than 137000, the retention force at high temperature and the adhesion relative to the low polarity adherend may deteriorate. In addition, if the above-mentioned peak molecular weight is greater than 300000, the adhesion relative to the low polarity adherend may sometimes deteriorate. From such a viewpoint, the above-mentioned peak molecular weight is preferably more than 138000 and less than 220000, more preferably more than 138000 and less than 200000. In addition, the peak molecular weight measured by GPC of the sol part of the adhesive is the value of the molecular weight that becomes the peak top in the molecular weight distribution obtained by GPC measurement, and can be measured by the method described in the embodiment described later. In addition, the peak molecular weight (Mtp) measured by GPC of the sol part is the peak molecular weight measured by GPC of the sol part of the polymer as the main component, and does not include the peak value from the tackifier (TF).
[0202] The peak top molecular weight of the sol portion of the adhesive measured by GPC can be adjusted by changing the molecular weight and molecular weight distribution of the polymer constituting the adhesive by changing the polymerization method, changing the amount of the crosslinking agent, or adding low molecular weight components such as oligomers.
[0203] <Sol fraction (Rsol)>
[0204] The sol fraction (Rsol) of the adhesive in the adhesive sheet of the present invention is below 90 mass %. If the sol fraction (Rsol) of the adhesive is higher than 90 mass %, the holding power may deteriorate at high temperatures. In addition, the sol fraction (Rsol) of the adhesive in the adhesive sheet of the present invention is preferably above 45 mass % and below 75 mass %. If the above-mentioned sol fraction (Rsol) is above 45 mass %, it is possible to further improve the bonding property to the low-polarity adherend while improving the biomass rate. In addition, if the above-mentioned sol fraction (Rsol) is below 75 mass %, it is possible to further improve the holding power at high temperatures while improving the biomass rate. From such a viewpoint, the above-mentioned sol fraction (Rsol) is more preferably above 50 mass % and below 70 mass %, and further preferably above 55 mass % and below 70 mass %, and more preferably above 58 mass % and below 70 mass %. In addition, the above-mentioned sol fraction (Rsol) can be measured by the method described in the embodiments described later. In addition, the sol fraction (Rsol) can be adjusted by changing the molecular weight and molecular weight distribution of the polymer constituting the adhesive by changing the polymerization method, by changing the amount of the crosslinking agent, or by adding low molecular weight components such as oligomers.
[0205] <Glass transition temperature (Tg)>
[0206] The glass transition temperature (Tg) of the adhesive in the adhesive sheet of the present invention is below 5°C. If the glass transition temperature (Tg) is higher than 5°C, the low-temperature adhesion may be deteriorated. From such a viewpoint, the glass transition temperature (Tg) is preferably below 2.5°C, more preferably below 0°C, and further more preferably below -1°C. The upper limit of the range of the glass transition temperature (Tg) is not particularly limited, but from the viewpoint of improving the holding power at high temperatures, it is preferably above -20°C, more preferably above -18°C, and further more preferably above -17°C. In addition, the glass transition temperature (Tg) can be measured by the method described in the examples described later. In addition, the glass transition temperature (Tg) can be adjusted by the type and amount of the monomer constituting the polymer of the adhesive. In addition, it can also be adjusted by the type and amount of the tackifier, for example, by using a tackifier with a high softening temperature or increasing the amount of the tackifier, the glass transition temperature (Tg) can be easily increased. The glass transition temperature (Tg) can also be adjusted by adding fine particles or the like.
[0207] <Hardness(S)>
[0208] The adhesive of the adhesive sheet of the present invention preferably has a hardness (S) of 50,000 or more and 180,000 or less, as represented by the following general formula (3). The hardness (S) is a parameter indicating the softness of the adhesive. If the hardness (S) is within a predetermined range, the adhesive exhibits excellent adhesion properties and is neither too soft nor too hard.
[0209] S=Mw×Rsol / D (3)
[0210] In the general formula (3), Mw represents the weight average molecular weight of the sol portion of the adhesive measured by GPC, Rsol represents the sol fraction in the adhesive, and D represents the dispersion of the sol portion of the adhesive measured by GPC.
[0211] If the hardness (S) is above 50,000, the holding power at high temperature and the bonding property to the low polarity adherend can be made better while improving the biomass rate. In addition, if the hardness (S) is below 180,000, the holding power at high temperature can be made better while improving the biomass rate. From such a viewpoint, the hardness (S) is more preferably above 55,000 and below 120,000, and further more preferably above 60,000 and below 112,000. In addition, the hardness (S) can be measured by the method described in the embodiments described later. In addition, the hardness (S) can be adjusted by changing the molecular weight and molecular weight distribution of the polymer constituting the adhesive by changing the polymerization method, or by changing the amount of the cross-linking agent, or by coordinating low molecular weight components such as oligomers.
[0212] <Dispersion (D)>
[0213] The dispersion (D) based on the sol part in the adhesive of the adhesive sheet of the present invention measured by GPC is preferably 1.6 or more and less than 3. When the dispersion (D) is above 1.6, the bonding property to the low-polarity adherend can be improved while improving the biomass rate. In addition, when the dispersion (D) is less than 3, the retention force at high temperature can be improved while improving the biomass rate. From this point of view, the dispersion (D) is more preferably 1.8 or more and less than 3, more preferably 1.9 or more and less than 3, and further more preferably 2.0 or more and less than 3. Note that the dispersion (D) can be measured by the method described in the following examples. In addition, the dispersion (D) of the sol part measured by GPC is the dispersion of the sol part of the polymer as the main component measured by GPC, and does not include the molecular weight caused by the peak from the thickener (TF).
[0214] The degree of dispersion (D) can be adjusted by changing the polymerization method to change the molecular weight of the polymer constituting the adhesive, changing the amount of the crosslinking agent added, or adding a low molecular weight component such as an oligomer.
[0215] <Weight average molecular weight (Mw)>
[0216] The weight average molecular weight (Mw) of the sol part of the adhesive in the adhesive sheet of the present invention measured by GPC is preferably more than 190,000 and less than 700,000. If the above-mentioned weight average molecular weight is more than 190,000 and less than 700,000, then the retention force at high temperature and the bonding property for low polarity adherends can be further improved while improving the biomass rate. From such a viewpoint, the above-mentioned weight average molecular weight (Mw) is more preferably more than 200,000 and less than 600,000, and further more preferably more than 220,000 and less than 550,000, and more preferably more than 240,000 and less than 460,000. In addition, the weight average molecular weight (Mw) can be measured by the method described in the embodiments described later. In addition, the weight average molecular weight (Mw) measured by GPC of the sol part is the weight average molecular weight measured by GPC of the sol part of the polymer as the main component, and does not include the molecular weight caused by the peak from the tackifier (TF).
[0217] The weight average molecular weight (Mw) can be adjusted by changing the polymerization method to change the molecular weight and molecular weight distribution of the polymer constituting the adhesive, by changing the amount of the crosslinking agent, or by adding a low molecular weight component such as an oligomer.
[0218] <Biological rate>
[0219] The adhesive in the adhesive sheet of the present invention preferably has a biogenic carbon content (hereinafter also referred to as "biorate") of 51% by mass or more. By making the biorate 51% or more, the adhesive can be used as a "biomass product". Biomass products can save petroleum resources by using renewable organic resources, and can also reduce carbon dioxide emissions generated by the combustion of petroleum products, thereby reducing the load on the environment. From these viewpoints, the biorate is more preferably 55% by mass or more, and even more preferably 60% by mass or more. In addition, the higher the biorate, the better, as long as it is below 100% by mass. In addition, the method for measuring the biorate has been described in the project of the first invention, so it is omitted.
[0220] <Polymer (X2)>
[0221] The adhesive in the adhesive sheet of the present invention preferably contains a polymer (X2). The polymer (X2) contains a structural unit derived from at least one monomer (Y2) selected from a monomer (A2) represented by the following general formula (4) and a monomer (B2) represented by the following general formula (5). In addition, in this specification, the term "monomer (Y2)" is also used to summarize the monomer (A2) and the monomer (B2).
[0222]
[0223] In the general formula (4), R 4 Indicates H or CH3, R 5 Indicates -C n H 2n+1 , n represents an integer of 7 to 20. In formula (5), R 6 Represents -C(=O)C m H 2m+1 , m represents an integer of 6 to 13. Note that the monomer (A2) represented by the general formula (4) is different from the monomer (A1) represented by the general formula (1) in that n represents an integer of 7 to 20, while the monomer (B2) represented by the general formula (5) is the same as the monomer (B1) represented by the general formula (2).
[0224] In the present invention, by including at least one of the structural units from monomer (A2) and monomer (B2), it is easy to make the holding power at high temperature, low temperature adhesion and bonding property to low polarity adherends all good. In addition, monomer (A2) and monomer (B2) are easy to manufacture from raw materials from organisms, and it is easy to improve the biomass rate described later.
[0225] The polymer (X2) may contain structural units derived from one or both of the monomers (A2) and (B2), but preferably contains structural units derived from the monomer (A2). If the polymer (X2) has structural units derived from the monomer (A2), the high temperature holding power, low temperature adhesion and bonding properties to low polarity adherends are easily improved.
[0226] R in formula (4) 5 The alkyl group (-C n H 2n+1 ) and R in formula (4) 6 The alkyl group (-C m H 2m+1 ) may be straight chain or branched chain, but is preferably straight chain from the viewpoint of high temperature holding power, low temperature adhesion, and adhesion to low polarity adherends. In addition, from the viewpoint of making it easy to improve high temperature holding power, low temperature adhesion, and adhesion to low polarity adherends, R 5 The n in formula (4) is preferably 7 to 18, more preferably 7 to 14, and still more preferably 7. In addition, from the viewpoint of achieving good adhesion performance, it is preferred that R in formula (4) 4 For H.
[0227] Therefore, the polymer (X2) preferably contains a compound derived from the general formula (4) wherein n is 7 to 18 and R 5 The structural unit of the linear monomer (A2) preferably contains a monomer derived from a monomer in which n is 7 and R 5 is a structural unit of a linear monomer (A2). In this case, the monomer (A2) is more preferably R 4 For H.
[0228] Specific examples of the monomer (A2) include n-heptyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, n-decyl (meth)acrylate, 2-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-undecyl (meth)acrylate, n-tetradecyl (meth)acrylate (myristyl (meth)acrylate), n-octadecyl (meth)acrylate, etc. These monomers (A2) may be used alone or in combination of two or more.
[0229] Specific examples of the monomer (B2) include vinyl decanoate, vinyl laurate, vinyl octanoate, vinyl nonanoate, etc. These monomers (B2) may be used alone or in combination of two or more.
[0230] Among the above-mentioned monomers (A2) and (B2), n-heptyl (meth)acrylate, n-tetradecyl (meth)acrylate, and n-octadecyl (meth)acrylate are preferred, and n-heptyl (meth)acrylate is more preferred. By using n-heptyl (meth)acrylate, n-tetradecyl (meth)acrylate, and n-octadecyl (meth)acrylate, it is easy to improve the holding power at high temperature, the adhesion at low temperature, and the bonding property to the low-polarity adherend.
[0231] Note that, in this specification, (meth)acrylate is used as a term representing one or both of acrylate and methacrylate, and the same applies to other similar terms.
[0232] In the above general formula (4) and general formula (5), R 5 and R 6 Preferably, the carbon is derived from organisms, especially plants. 5 and R 6 Carbon from organisms can improve the biomass rate described below. 5 and R 6 The monomers (A2) and (B2) are respectively derived from carbon of biological origin and can be obtained easily and cheaply by using saturated fatty acids and unsaturated fatty acids collected from animals and plants as raw materials and alcoholizing and esterifying them.
[0233] In the present invention, the content of the structural unit derived from the monomer (Y2) (i.e., at least one monomer selected from the monomer (A2) and the monomer (B2)) in the polymer (X2) is preferably 48% by mass or more. If the content is 48% by mass or more, it is easy to improve the biomass rate while making the retention at high temperature, the low temperature adhesion and the bonding property to the low-polarity adherend all good.
[0234] From the viewpoint of improving the above-mentioned various properties while improving the biomass rate, the content of the structural unit derived from the monomer (Y2) is preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In addition, the content of the structural unit derived from the monomer (Y2) is preferably 99% by mass or less, more preferably 98% by mass or less, and further preferably 97.5% by mass or less in order to contain a monomer containing a functional group, such as that described later, in a predetermined amount.
[0235] In addition, as described above, the monomer (A2) preferably contains at least one (meth)acrylate selected from n-heptyl (meth)acrylate, n-tetradecyl (meth)acrylate, and n-octadecyl (meth)acrylate. In the polymer (X2), the content of the structural units derived from these (meth)acrylates is preferably 48% by mass or more, more preferably 70% by mass or more, further more preferably 80% by mass or more, and particularly preferably 90% by mass or more, from the viewpoint of improving the above-mentioned various properties while improving the biomass rate. In addition, the content of the structural units derived from these (meth)acrylates is preferably 99% by mass or less, more preferably 98% by mass or less, and further more preferably 97.5% by mass or less.
[0236] In addition, the monomer (A2) preferably contains n-heptyl (meth)acrylate, and from the viewpoint of tanδ (23°C) and the viewpoint of improving the above-mentioned various properties while improving the biomass rate, it is more preferable to contain n-heptyl (meth)acrylate as the main monomer. The content of the structural unit derived from n-heptyl (meth)acrylate in the polymer (X2) is specifically preferably 48% by mass or more, more preferably 70% by mass or more, further more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In addition, the content of the structural unit derived from n-heptyl (meth)acrylate is preferably 99% by mass or less, more preferably 98% by mass or less, and further more preferably 97.5% by mass or less. Note that n-heptyl (meth)acrylate is preferably n-heptyl acrylate.
[0237] Polymer (X2) preferably comprises the structural unit from other monomers except above-mentioned monomer (A2) and monomer (B2).Other monomers can be monomers with polymerizable carbon-carbon double bonds such as vinyl, (meth) acryloyl.As other monomers, preferably monomers containing polar groups (hereinafter also referred to as "polar group-containing monomer (C)").By polymer (X2) containing the structural unit from polar group-containing monomer (C), it is easy to improve the bonding force of adhesive, and it is also easy to improve the holding power under high temperature, low temperature adhesion and the bonding property for low polarity adherend etc.
[0238] The polar group is a functional group having active hydrogen, and specifically, carboxyl, hydroxyl, amino, amide, etc. can be listed. The polar group can also be a functional group that can react with a crosslinking agent described later. The polar group-containing monomer (C) can be used alone or in combination of two or more. In addition, the polar group-containing monomer (C) is the same as that described in the project of the first invention, so the description is omitted.
[0239] The weight average molecular weight (Mw) of polymer (X2) is preferably more than 200,000 and less than 1,100,000. If the weight average molecular weight (Mw) is set to more than 200,000, the shear strength of the adhesive can be improved, thereby improving the holding power of the adhesive at high temperatures. In addition, if it is less than 1,100,000, the adhesion of the adhesive can be made good, and the low-temperature adhesion and the bonding properties to the low-polarity adherend can be more easily improved.
[0240] From these viewpoints, the weight average molecular weight (Mw) is more preferably 300,000 or more, and even more preferably 400,000 or more, and is more preferably 1,050,000 or less, and even more preferably 1,000,000 or less.
[0241] The weight average molecular weight (Mw) can be appropriately adjusted by appropriately selecting the amount of the polymerization initiator used, polymerization conditions such as the polymerization temperature, the polymerization method, and the like.
[0242] In addition, the weight average molecular weight is a weight average molecular weight converted into standard polystyrene measured by gel permeation chromatography (GPC).
[0243] The polymer (X2) is a main component in the adhesive. In order to impart appropriate adhesive properties, the content of the polymer (X2) in the adhesive is, for example, 50% by mass or more, preferably 60% by mass or more, and more preferably 65% by mass or more. In addition, in order to be able to mix a prescribed amount of components other than the polymer (X2) such as a tackifier and a cross-linking agent in the adhesive, the polymer (X2) in the adhesive is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less.
[0244] Since the low molecular weight components of the polymer (X2) become the sol part, the molecular weight and molecular weight distribution of the polymer (X2) can be changed by changing the polymerization method, thereby adjusting the above-mentioned properties of the sol part of the adhesive. In addition, by changing the amount of the cross-linking agent, the low molecular weight components of the polymer (X2) are not cross-linked and remain in the adhesive, so by changing the amount of the cross-linking agent, the above-mentioned properties of the sol part of the adhesive can be adjusted. For example, as the low molecular weight components of the polymer (X2), oligomers derived from monomers that are raw materials for the polymer (X2) can be listed.
[0245] <Method for producing polymer (X2)>
[0246] The polymer (X2) can be obtained by subjecting a mixture of the above-mentioned raw monomers to a radical reaction in the presence of a polymerization initiator. Therefore, the molecular weight distribution of the polymer (X2) can be quite broad, and the sol fraction can be increased.
[0247] The mode of free radical reaction is not particularly limited, and examples thereof include free radical polymerization, active free radical polymerization, etc. Free radical polymerization can expand the molecular weight distribution compared with active free radical polymerization, thereby increasing the amount of low molecular weight components generated. As a result, the sol portion of the above-mentioned adhesive can be further increased, and while improving the biomass rate, the retention force at high temperature, the low temperature adhesion, and the bonding property to the low polarity adherend can all be improved. The polymerization method is not particularly limited, and conventionally known methods can be used. For example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. can be listed. Among them, solution polymerization is preferred because the synthesis is simple. In addition, since the method for producing polymer (X2) is the same as the method for producing polymer (X1) described in the project of the first invention, the description is omitted.
[0248] In the adhesive in the adhesive sheet of the present invention, a low molecular weight component (Z) can be added to the polymer obtained by the above-mentioned manufacturing method to form a polymer (X2). As mentioned above, by changing the molecular weight and molecular weight distribution of the polymer (X2) by a polymerization method, the above-mentioned characteristics of the sol part of the adhesive in the adhesive sheet of the present invention can be adjusted to the above-mentioned range. However, even if a low molecular weight component (Z) is used, the above-mentioned characteristics of the sol part of the adhesive in the adhesive sheet of the present invention can be adjusted to enter the above-mentioned range. In addition, the low molecular weight component (Z) also has the function of a tackifier.
[0249] The low molecular weight component (Z) is preferably an oligomer of a monomer used as a raw material of the above-mentioned polymer (X2). Therefore, the low molecular weight component (Z) is preferably an oligomer containing a structural unit derived from at least one monomer (Y2) selected from the monomer (A2) represented by the above-mentioned general formula (4) and the monomer (B2) represented by the above-mentioned general formula (5). In addition, the monomer used in the low molecular weight component (Z) has been described in the above-mentioned item of the polymer (X2), so the description of the monomer used in the low molecular weight component (Z) is omitted.
[0250] As with the polymer (X2), among the above-mentioned monomers (A2) and (B2), n-heptyl (meth)acrylate, tetradecyl (meth)acrylate, and octadecyl (meth)acrylate are preferred, among which n-heptyl (meth)acrylate is more preferred, and n-heptyl acrylate is further preferred. Therefore, the low molecular weight component (Z) is preferably an oligomer of n-heptyl (meth)acrylate, an oligomer of tetradecyl (meth)acrylate, and an oligomer of octadecyl (meth)acrylate, among which an oligomer of n-heptyl (meth)acrylate is more preferred, and an oligomer of n-heptyl acrylate is further preferred.
[0251] The content of the low molecular weight component (Z) in the polymer (X2) is not particularly limited, and may be appropriately adjusted so that various properties of the gel fraction fall within the above ranges.
[0252] <Thickener>
[0253] The adhesive in the adhesive sheet of the present invention preferably contains a tackifier in addition to the above-mentioned polymer (X2). In addition, the tackifier added to the polymer (X2) is the same as the tackifier added to the polymer (X1) described in the first invention except for the content described below, so its description is omitted.
[0254] If adhesive comprises tackifier, then the content of tackifier is not particularly limited, but relative to polymer (X2) 100 mass parts, preferably 10 mass parts or more and 50 mass parts or less. If the content of tackifier is above the above lower limit, then it is easy to make low temperature adhesion and the bonding property relative to low polarity adherend good. In addition, by below the above upper limit, it is possible to prevent the holding force at high temperature from reducing. From the above viewpoint, in the second invention, the content of tackifier is preferably below 40 mass parts above 12 mass parts, more preferably below 30 mass parts above 14 mass parts.
[0255] <Cross-linking agent>
[0256] The adhesive in the adhesive sheet of the present invention is preferably cross-linked with a cross-linking agent. That is, the adhesive is preferably a cross-linked adhesive composition containing a cross-linking agent in addition to the above-mentioned polymer (X2) or polymer (X2) and tackifier. In addition, the cross-linking agent added to the polymer (X2) is the same as the cross-linking agent added to the polymer (X1) described in the project of the first invention, except for the amount of the cross-linking agent as described below, so the description is omitted.
[0257] The amount of the crosslinking agent added to the adhesive can be appropriately changed depending on the type of polymer (X2), the desired physical properties such as the degree of crosslinking, etc., but in the second invention, for 100 parts by mass of the polymer (X2), it is, for example, not less than 0.1 parts by mass and not more than 20 parts by mass, preferably not less than 0.5 parts by mass and not more than 8 parts by mass, and more preferably not less than 0.6 parts by mass and not more than 4 parts by mass.
[0258] <Other additives>
[0259] The adhesive in the adhesive sheet of the present invention may contain additives such as silane coupling agents, antioxidants, ultraviolet protection agents, plasticizers, emulsifiers, softeners, fillers, pigments, dyes, etc. as needed. Even these additives are preferably selected from materials derived from organisms within the possible range from the viewpoint of improving the bioavailability.
[0260] <Adhesive Preparation>
[0261] The adhesive in the adhesive sheet of the present invention can be formed by the adhesive composition, for example, by preparing the adhesive composition. The adhesive composition is composed of components for forming the adhesive. The adhesive composition preferably comprises the above-mentioned polymer (X2). The adhesive composition can further comprise a tackifier, a cross-linking agent, other additives, etc. as required. The adhesive composition can also be diluted by a diluent solution such as an organic solvent. The diluent solution can be a solvent used when synthesizing the polymer (X2), or a solution added after synthesizing the polymer (X2).
[0262] The adhesive composition can be cross-linked by heating and drying as needed to form an adhesive. The adhesive is an adhesive used in the adhesive sheet of the present invention. By appropriately setting the heating temperature during cross-linking, the peak top molecular weight of the sol part can be appropriately adjusted.
[0263] The heating temperature during cross-linking is not particularly limited, and is, for example, 90°C to 130°C, preferably 100°C to 120°C. In addition, the heating time is, for example, 30 seconds to 10 minutes, preferably 1 minute to 5 minutes. In addition, in order to further proceed with the cross-linking reaction, it is preferred to age the adhesive after drying. The aging temperature is preferably 20°C to 60°C, more preferably 30°C to 50°C. In addition, the aging time is preferably 1 day to 10 days, more preferably 2 days to 5 days.
[0264] <Adhesive sheet>
[0265] The adhesive sheet of the present invention comprises the above-mentioned adhesive, and specifically comprises an adhesive layer composed of the above-mentioned adhesive. The adhesive sheet may be an adhesive sheet without a substrate or an adhesive sheet with a substrate, but an adhesive sheet with a substrate is preferred.
[0266] An adhesive sheet without a substrate is, for example, a non-supported tape. A non-supported tape is a double-sided tape used in a single-layer state of an adhesive layer without a substrate. An adhesive sheet with a substrate is, for example, an adhesive tape. The adhesive tape includes a substrate and an adhesive layer disposed on at least one surface of the substrate. In this case, the adhesive tape may be a double-sided tape with an adhesive layer disposed on both sides of the substrate, or may be a single-sided tape with an adhesive layer disposed only on one side of the substrate.
[0267] In the double-sided tape having adhesive layers on both sides of a substrate, the adhesive layer on at least one side may be composed of the above-mentioned adhesive.
[0268] In the adhesive sheet, a release sheet can be appropriately attached to the surface of the exposed adhesive layer for protection. The release sheet is a material having a release agent coated on at least one surface of a release sheet substrate to form a release surface, and can be attached by bringing the release surface into contact with the adhesive layer.
[0269] [Base material]
[0270] The substrate used for the adhesive sheet is not particularly limited, but is preferably a resin film, a nonwoven fabric or a foam. In addition, the substrate used in the adhesive sheet is the same as the substrate of the adhesive tape described in the first invention, so description is omitted.
[0271] In the adhesive sheet, the thickness of the adhesive layer is not particularly limited, and is preferably 5 μm to 200 μm, and preferably 10 μm to 100 μm. When the thickness of the adhesive layer is within this range, the obtained adhesive sheet can exhibit sufficient adhesive strength.
[0272] The total thickness of the adhesive sheet (the sum of the thickness of the substrate and the adhesive layer) is preferably 10 μm to 2200 μm. When the total thickness of the adhesive sheet is within this range, the obtained adhesive sheet can exhibit sufficient adhesive strength.
[0273] (Viscosity value)
[0274] The adhesive of the adhesive sheet of the present invention preferably has a tape peeling limit value of 90 gf·s or more at 23° C. as measured by a tack test. The tack test was performed as follows.
[0275] First, apply a 50 μm thick adhesive layer on a 23 μm thick PET substrate, and place the tape with the adhesive layer facing upward on a plate set at 23°C in a viscosity tester (e.g., TAC-1000 produced by Reska). Fix the tape from above with the sample control provided by the viscosity tester. Then, press a 5 mm diameter cylindrical stainless steel probe against the tape at a probe temperature of 23°C, a pressing speed of 5 mm / s, and a pressing load of 100 gf, and keep it in this state for 10 seconds. After that, lift the probe at a lifting speed of 5 mm / s. Measure the force applied to the tape during this period.
[0276] In the above description, an example in which a tape is formed by an adhesive is described. However, even when no tape is formed, the same measurement can be performed by placing an adhesive on a plate set at 23° C. in a tack tester.
[0277] The above-mentioned peeling limit value is the integral value from time T1 when the force is displayed as 0 to the time when the maximum force (peak top) is displayed in the force-time curve showing the force applied to the tape at 23°C obtained by the above-mentioned adhesion test. In the adhesion test, when the probe is pressed on the tape, the force-time curve drops, and then when the probe starts to be lifted, the force-time curve gradually rises. The integral value from time T1 when the force is displayed as 0 to time T2 when the maximum force (peak top) is calculated and used as the peeling limit value.
[0278] By adjusting the peeling limit value to the above range, the peeling of the tape can be suppressed even under high temperature and high humidity and under the condition of restoring force. The preferred lower limit of the peeling limit value is 100 gf·s, and the more preferred lower limit is 110 gf·s. In addition, the upper limit of the peeling limit value is not particularly limited.
[0279] <Biological rate>
[0280] The adhesive sheet of the present invention, from the same viewpoint as the above-mentioned adhesive, preferably has a biomass rate of more than 40% by mass, more preferably more than 50% by mass, and even more preferably more than 60% by mass. In addition, the higher the biomass rate, the better, as long as it is below 100% by mass. In addition, the biomass rate of an adhesive sheet generally varies depending on the different components (e.g., adhesive layer and substrate). Therefore, the biomass rate can be calculated by finding the biomass rate of each component and taking a weighted average using the mass of each component as a weight.
[0281] (Method for producing adhesive sheet)
[0282] The method for producing the adhesive sheet is not particularly limited, and the adhesive sheet can be produced by a conventionally known method. Note that the method for producing the adhesive sheet is the same as the method for producing the adhesive tape described in the first invention, and thus the description thereof is omitted.
[0283] (Application of adhesive sheet)
[0284] The use of the adhesive sheet of the present invention is not particularly limited, but is preferably used in electrical products and vehicles. Note that since the method for producing the adhesive sheet is the same as the use of the adhesive and tape described in the first invention, the description thereof is omitted.
[0285] The present invention may be a combination of the first invention and the second invention.
[0286] Example
[0287] Hereinafter, the present invention will be described based on examples, but the present invention is not limited to the scope of the examples.
[0288] <First Embodiment>
[0289] [Measurement and evaluation methods]
[0290] The measurement and evaluation of various physical properties were carried out according to the following procedures.
[0291] <Elastic modulus>
[0292] The storage modulus G', loss modulus G" and glass transition temperature (Tg) at each temperature can be measured under the following conditions using a polymer dynamic viscoelasticity measuring apparatus "itkDVA-200" (manufactured by ITI Measurement & Control Co., Ltd.).
[0293] Measuring mode: Shear
[0294] Heating rate: 5℃ / min
[0295] Measuring temperature range: -30~150℃
[0296] Set strain: 0.1%
[0297] Frequency: 10Hz
[0298] The measurement samples were prepared by molding the adhesive composition solution in each example in the present embodiment and the comparative example so that the final sample shape was 0.1 mm in thickness, 0.6 mm in width, and 10 mm in length, and heating and drying them under the same conditions as when forming the adhesive layer in each example.
[0299] <Weight average molecular weight>
[0300] The weight average molecular weight (Mw) of the polymer (X1) was measured by a GPC device "HLC822GPC" (produced by Tosoh Corporation) and obtained as a polystyrene conversion value. Specifically, the obtained polymer (X1) was diluted 50 times with tetrahydrofuran (THF), and the obtained dilution was filtered with a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare a measurement sample. The measurement sample was provided to a gel permeation chromatograph (produced by Waters, 2690Separations Model), and GPC measurement was performed under the conditions of a sample flow rate of 1 ml / min and a column temperature of 40°C to measure the polystyrene conversion molecular weight of the polymer (X1) to obtain a weight average molecular weight.
[0301] <Degree of cross-linking>
[0302] The adhesive (sample) W1 (g) was collected, and the collected sample was immersed in ethyl acetate at 23°C for 24 hours, and then the insoluble part was filtered out with a 200-mesh metal mesh. The residue on the metal mesh was dried at 110°C for 1 hour, and the mass after drying W2 (g) was measured, and the gel fraction (crosslinking degree) was calculated by the following formula.
[0303] Gel fraction (mass %) = 100 × W2 / W1
[0304] <Biological rate>
[0305] The bioavailability of the adhesive was measured according to ASTM 6866.
[0306] <Low temperature adhesion>
[0307] Based on the "double-sided tape (double-sided adhesive tape)" described in JIS Z-1528, one side of the double-sided tape cut to a width of 25 mm and a length of 100 mm was attached to a polypropylene plate (manufactured by Takiron Corporation, PP1300) with a thickness of 2 mm, a width of 50 mm, and a length of 100 mm at 0°C, so that the bonding length was 75 mm. After backing the other side of the double-sided tape with a PET film, a 2kg roller was pressed back and forth once at 0°C to prepare an adhesive test piece. After the obtained adhesive test piece was placed in an atmosphere of 0°C for 60 minutes, it was stretched at a tensile speed of 200 mm / min under a 0°C environment using an Instron tensile tester, and the adhesive test piece was peeled off from the polypropylene plate at a peeling angle of 180° to measure the peel strength (N / 25mm). Based on the results of the peel strength, the low-temperature adhesion was evaluated according to the following evaluation criteria.
[0308] A: Peel strength is above 5N / 25mm.
[0309] B: The peel strength is 3 N / 25 mm or more and less than 5 N / 25 mm.
[0310] C: Less than 3N / 25mm.
[0311] <PP Adhesion Strength>
[0312] Based on the "double-sided tape (double-sided adhesive tape)" described in JIS Z-1528, one side of the double-sided tape cut to a width of 25 mm and a length of 100 mm was attached to a polypropylene plate (manufactured by Takiron Corporation, PP1300) with a thickness of 2 mm, a width of 50 mm, and a length of 100 mm at 23°C and 50% RH, so that the bonding length was 75 mm. After backing the other side of the double-sided tape with a PET film, a 2kg roller was moved back and forth once at 23°C and 50% RH for crimping to prepare an adhesive test piece. After placing the obtained adhesive test piece in an atmosphere of 23°C and 50% RH for 20 minutes, it was stretched at a tensile speed of 200 mm / min using an Instron tensile tester, and the adhesive test piece was peeled off from the polypropylene plate at a peeling angle of 180°, and the peel strength (N / 25mm) was measured at 23°C. Based on the peel strength results, the PP adhesive strength was evaluated according to the following evaluation criteria.
[0313] A: Peel strength is above 15N / 25mm.
[0314] B: The peel strength is 10 N / 25 mm or more and less than 15 N / 25 mm.
[0315] C: Peel strength is less than 10N / 25mm.
[0316] <Retention strength at high temperatures>
[0317] Based on JIS Z-1528, one side of a double-sided tape with a width of 25 mm and a length of 100 mm was attached to a cold-rolled stainless steel plate (SUS304 plate) with a thickness of 1.5 mm, a width of 25 mm and a length of 100 mm at 23°C, so that the bonding length was 25 mm, and a double-sided tape with a length of 75 mm protruded from the end of the SUS304 plate, so that the two sides were staggered in the length direction. After that, the other side of the double-sided tape was backed with a PET film, and a 2 kg roller was pressed back and forth once to prepare an adhesion test piece.
[0318] After the obtained bonding test piece was placed in an atmosphere of 23°C and 50% RH for 20 minutes, the bonding test piece was vertically hung in a constant temperature dryer at 40°C for 1 hour with the extended double-sided tape side at the bottom. Next, a load of 1 kg was applied to the lower end of the double-sided tape, and the test piece was vertically hung at 40°C for 24 hours, and the offset distance (mm) of the bonding part after 1 hour was measured. Evaluation was performed according to the following evaluation criteria based on the offset distance.
[0319] A: The offset distance is less than 0.5mm.
[0320] B: The offset distance is 0.5 mm or more and less than 2 mm.
[0321] C: The offset distance is more than 2 mm.
[0322] The components used in Examples and Comparative Examples are as follows.
[0323] <Single substance (A1)>
[0324] (Main monomer)
[0325] Heptyl acrylate (HA(C7)):
[0326] Heptyl acrylate (HA(C7)) is R 2 A compound derived from biomass carbon, produced by the esterification reaction of acrylic acid and n-heptanol. n-heptanol is produced by decomposing ricinoleic acid in castor oil.
[0327] (Comonomer)
[0328] 2-Ethylhexyl acrylate (2EHA): Produced by Mitsubishi Chemical Corporation
[0329] <Other monomers>
[0330] Butyl acrylate (BA): Produced by Mitsubishi Chemical Corporation
[0331] Acrylic acid (AAc): Produced by Nippon Shokubai Co., Ltd.
[0332] 2-Hydroxyethyl acrylate (HEA): Produced by Osaka Organic Chemical Industry Co., Ltd.
[0333] <Thickener (TF)>
[0334] Polymerized rosin ester resin, hydroxyl value 46, softening temperature 150°C, biogenic carbon content 95% by mass
[0335] <Cross-linking agent>
[0336] Polyisocyanate crosslinking agent, "Coronet L-45" manufactured by Tosoh Corporation
[0337] (Example 1)
[0338] [Synthesis of polymer (X1)]
[0339] Ethyl acetate was added to the reaction vessel as a polymerization solvent, and after bubbling with nitrogen, the reactor was heated while nitrogen was introduced to start reflux. Next, 0.1 parts by mass of azobisisobutyronitrile was diluted 10 times with ethyl acetate as a polymerization initiator, and the obtained polymerization initiator solution was added to the reactor, and 96.9 parts by mass of n-heptyl acrylate (HA(C7)), 2.9 parts by mass of acrylic acid (AAc), and 0.2 parts by mass of 2-hydroxyethyl acrylate (HEA) were added dropwise over 2 hours. After the dropwise addition was completed, 0.1 parts by mass of azobisisobutyronitrile as a polymerization initiator was diluted 10 times with ethyl acetate, and the obtained polymerization initiator solution was again added to the reactor, and a polymerization reaction was carried out for 4 hours to obtain a solution containing polymer (X1). The weight average molecular weight of the obtained polymer (X1) was measured, and the result was 600,000.
[0340] [Making double-sided tape]
[0341] In the obtained solution containing the polymer (X1), 0.8 parts by mass of a crosslinking agent and 15 parts by mass of a tackifier were added relative to 100 parts by mass of the polymer (X1) to prepare an adhesive composition solution. The adhesive composition solution was applied to the release surface of a release sheet subjected to a release treatment on one side, and heated to dry it to form an adhesive layer. The obtained adhesive layer was transferred to both sides of a nonwoven fabric as a substrate to obtain a double-sided tape having adhesive layers provided on both sides of the substrate.
[0342] Adhesive was collected from the adhesive layer of the obtained double-sided tape to measure the degree of crosslinking and bioavailability. In addition, a measurement sample was prepared from the adhesive composition solution, and the storage modulus G', loss modulus G" and glass transition temperature (Tg) were measured. In addition, the double-sided tape was used to evaluate low-temperature adhesion, PP adhesion and holding power at high temperature. The evaluation results are shown in Table 2.
[0343] (Examples 2 and 3)
[0344] The same procedure as in Example 1 was carried out except that the amounts of the tackifier (TF) and the crosslinking agent were changed to parts by mass as shown in Table 1.
[0345] (Example 4)
[0346] In the production of the polymer (X1), the same procedure as in Example 1 was carried out except that the polymerization reaction time was changed to 5 hours.
[0347] (Example 5)
[0348] In the production of polymer (X1), the same procedures as in Example 1 were carried out except that the polymerization reaction time was changed to 5.5 hours and the amount of the crosslinking agent was changed to parts by mass as shown in Table 1.
[0349] (Example 6)
[0350] The same procedure as in Example 1 was carried out except that the amounts of monomers in preparing the polymer (X1) were changed to the ratios shown in Table 1 and the amounts of the tackifier (TF) and the crosslinking agent were changed to the parts by mass shown in Table 1.
[0351] (Comparative Example 1)
[0352] In the production of polymer (X1), the polymerization reaction time was changed to 7 hours. In addition, the same procedure as in Example 1 was carried out except that the blending amounts of the tackifier (TF) and the crosslinking agent were changed to the parts by mass shown in Table 1.
[0353] (Comparative Example 2)
[0354] In the production of polymer (X1), the polymerization reaction time was changed to 2.5 hours. In addition, the same procedure as in Example 1 was carried out except that the amounts of the tackifier (TF) and the crosslinking agent were changed to the parts by mass shown in Table 1.
[0355] (Comparative Example 3)
[0356] The same procedure as in Example 1 was carried out except that the types and amounts of monomers used in preparing the polymer (X1) were changed as shown in Table 1 and the amounts of the tackifier (TF) and the crosslinking agent were changed to the parts by mass shown in Table 1.
[0357] Table 1
[0358]
[0359] ※Molecular weight is weight average molecular weight (Mw).
[0360] ※The mass parts of monomers are values when the total amount of monomers blended when synthesizing the polymer (X1) is set to 100 mass parts. It can be considered that the polymer (X1) contains the structural units derived from the monomers listed in Table 1 in the amounts listed in Table 1.
[0361] * The amounts of the tackifier (TF) and the crosslinking agent are parts by mass relative to 100 parts by mass of the polymer (X1).
[0362] Table 2
[0363]
[0364] In each of the above examples, the adhesive contains a polymer (X1) having a predetermined amount or more of a structural unit derived from the monomer (A1), and the tanδ (23°C) is set to 0.8 to 1.3, thereby achieving good retention at high temperatures, low-temperature adhesion, and adhesion to a low-polarity adherend (polypropylene resin). In contrast, in each of the comparative examples, the polymer (X1) does not contain a predetermined amount or more of a structural unit derived from the monomer (A1), or the tanδ (23°C) is out of the range, so that the retention at high temperatures, low-temperature adhesion, and adhesion to a low-polarity adherend (polypropylene resin) cannot be improved while the biomass rate is increased.
[0365] <Second Embodiment>
[0366] [Measurement and evaluation methods]
[0367] The measurement and evaluation of various physical properties were carried out according to the following procedures.
[0368] <Peak top molecular weight (Mtp)>
[0369] The adhesive collected from the tape is immersed in tetrahydrofuran (THF) and vibrated and immersed for 24 hours at room temperature. Then, a sample of the above-mentioned adhesive is taken out through a 200-mesh filter, and the impregnation solution is filtered through an optical filter, and the obtained filtrate becomes a sample solution containing the sol part of the above-mentioned adhesive. The obtained sample solution is provided to a gel permeation chromatography (GPC, such as "e2695" produced by Waters), and tetrahydrofuran (THF) is used as the mobile phase, and GPC measurement is performed under the conditions of a sample flow rate of 1mL / min and a column temperature of 40°C, and the molecular weight distribution of the polystyrene-converted molecular weight is determined. As a column, for example, two "GPC KF-806L" produced by Shodex are connected and used. According to the obtained molecular weight distribution curve, the peak top molecular weight (Mtp) of the sol part of the adhesive measured by GPC is calculated. In addition, it is regarded as a peak of GPC that does not contain a thickener (TF). Therefore, the peak top molecular weight (Mtp) of the sol portion of the adhesive measured by GPC is the peak top molecular weight of the sol portion of the polymer that is the main component of the adhesive measured by GPC.
[0370] <Weight average molecular weight (Mw), dispersion (D), sol fraction (Rsol) and hardness (S)>
[0371] Similar to the measurement of the above-mentioned peak molecular weight (Mtp), GPC was used to measure the weight average molecular weight and the number average molecular weight of the sol part of the adhesive. Then, the weight average molecular weight obtained was divided by the number average molecular weight to calculate the dispersity (D) of the sol part. In addition, the gel fraction was measured by the following method, and the gel fraction was deducted from 100% by mass to calculate the sol fraction (Rsol). Above, the soft and hardness (S) was calculated according to the weight average molecular weight (Mw), dispersity (D) and sol fraction (Rsol) obtained. In addition, it is considered as the peak of the GPC that does not include tackifier (TF). Therefore, the weight average molecular weight (Mw) and the dispersity (D) of the sol part of the adhesive are the weight average molecular weight and the dispersity of the sol part of the polymer as the main component of the adhesive.
[0372] The adhesive (sample) W1 (g) was collected and immersed in THF at 23°C for 24 hours, and the insoluble part was filtered with a 200-mesh metal mesh. The residue on the metal mesh was dried at 110°C for 1 hour, and the mass after drying W2 (g) was measured, and the gel fraction was calculated according to the following formula.
[0373] Gel fraction (mass %) = 100 × W2 / W1
[0374] <Glass transition temperature (Tg)>
[0375] The glass transition temperature (Tg) was measured in the same method as that of the first example.
[0376] <Biological rate>
[0377] The bioavailability of the adhesive was measured according to ASTM 6866.
[0378] <Elastic modulus>
[0379] The storage modulus G′ and loss modulus G″ at each temperature were measured under the same conditions as the elastic modulus measurement method of the first embodiment. In addition, regarding the storage modulus G′, loss modulus G″ and tan δ at each temperature, only the results of some examples and comparative examples are shown.
[0380] <PP Adhesion Strength>
[0381] The peel strength (N / 25 mm) at 23° C. was measured in the same manner as the PP adhesive strength of Example 1. Based on the peel strength results, the PP adhesive strength was evaluated according to the following evaluation criteria.
[0382] A: Peel strength is above 13N / 25mm.
[0383] B: The peel strength is 10 N / 25 mm or more and less than 13 N / 25 mm.
[0384] C: Peel strength is less than 10N / 25mm.
[0385] <Retention strength at high temperatures>
[0386] The offset distance (mm) of the bonded portion after one hour was measured in the same manner as the holding force at high temperature in Example 1. Based on the offset distance, evaluation was performed according to the following evaluation criteria.
[0387] A: The offset distance is less than 0.5mm.
[0388] B: The offset distance is greater than 0.5 mm and less than 1 mm.
[0389] C: The offset distance is more than 1 mm.
[0390] <Low temperature adhesion>
[0391] The low-temperature adhesion was evaluated in the same manner as that of the first example.
[0392] The components used in Examples and Comparative Examples are as follows.
[0393] <Single substance (A2)>
[0394] (Main monomer)
[0395] Heptyl acrylate (HA(C7)):
[0396] Heptyl acrylate (HA(C7)) is R 5 A carbon compound derived from plants, produced by the esterification reaction of acrylic acid and n-heptanol. n-heptanol is produced by decomposing ricinoleic acid from castor oil.
[0397] <Other monomers>
[0398] Acrylic acid (AAc): Produced by Nippon Shokubai Co., Ltd.
[0399] 2-Hydroxyethyl acrylate (HEA): Produced by Osaka Organic Chemical Industry Co., Ltd.
[0400] <Thickener (TF)>
[0401] Polymerized rosin ester resin, hydroxyl value 46, softening temperature 150°C, plant-derived carbon content 95% by mass
[0402] <Cross-linking agent>
[0403] Polyisocyanate crosslinking agent
[0404] (Example 7)
[0405] [Synthesis of polymer (X2)]
[0406] Ethyl acetate was added to the reaction vessel as a polymerization solvent, and after bubbling with nitrogen, the reactor was heated while nitrogen was introduced to start reflux. Next, a polymerization initiator solution obtained by diluting 0.1 mass parts of azobisisobutyronitrile as a polymerization initiator with ethyl acetate by 10 times was added to the reactor, and 96.9 mass parts of n-heptyl acrylate (HA(C7)), 2.9 mass parts of acrylic acid (AAc), and 0.2 mass parts of 2-hydroxyethyl acrylate (HEA) were added dropwise over 2 hours. After the dropwise addition was completed, 0.1 mass parts of azobisisobutyronitrile as a polymerization initiator was diluted 10 times with ethyl acetate, and the obtained polymerization initiator solution was put into the reactor again, and a polymerization reaction was carried out for 3.5 hours to obtain a solution containing polymer (X2). The weight average molecular weight of the obtained polymer (X2) was measured, and the result was 500,000.
[0407] [Making double-sided tape]
[0408] In the obtained solution containing the polymer (X2), 25 parts by mass of a thickener and 2.4 parts by mass of a crosslinking agent were added relative to 100 parts by mass of the polymer (X2) to prepare an adhesive composition solution. The adhesive composition solution was applied to the release surface of a release sheet subjected to a release treatment on one side, and heated to dry, and heated at 100° C. for 3 minutes to dry, to form an adhesive layer. The obtained adhesive layer was transferred to both sides of a nonwoven fabric as a substrate, to obtain a double-sided tape having adhesive layers provided on both sides of the substrate.
[0409] The adhesive layer of the obtained double-sided tape was collected to measure the peak molecular weight (Mtp), weight average molecular weight (Mw), dispersion (D), sol fraction (Rsol), hardness (S) and biomass rate. In addition, the adhesive composition solution was used to make a test sample and the glass transition temperature (Tg) was measured. In addition, the double-sided tape was used to evaluate the PP bonding force, the holding power at high temperature and the low temperature adhesion. The evaluation results are shown in Table 2.
[0410] (Examples 8 and 9)
[0411] The same procedure as in Example 1 was carried out except that the amounts of the tackifier (TF) and the crosslinking agent were changed to parts by mass as shown in Table 3.
[0412] (Examples 10 to 14)
[0413] In the production of polymer (X2), the polymerization reaction time was changed to change the weight average molecular weight of polymer (X2) from 500,000 to 800,000. Also, the blending amounts of tackifier (TF) and crosslinking agent were changed to the parts by weight shown in Table 3. Other than that, the same procedures as in Example 1 were followed.
[0414] (Examples 15 to 17)
[0415] In the production of polymer (X2), the polymerization reaction time was changed to change the weight average molecular weight of polymer (X2) from 500,000 to 1,000,000. Also, the blending amounts of tackifier (TF) and crosslinking agent were changed to the parts by mass shown in Table 3. Other than that, the same procedures as in Example 1 were followed.
[0416] (Comparative Example 4)
[0417] In the production of polymer (X2), the polymerization reaction time was changed to change the weight average molecular weight of polymer (X2) from 500,000 to 800,000. In addition, the blending amount of tackifier (TF) was changed to the parts by mass shown in Table 3. Other than this, the same procedures as in Example 1 were followed.
[0418] (Comparative Example 5)
[0419] The same procedure as in Example 1 was carried out except that the amounts of the tackifier (TF) and the crosslinking agent were changed to parts by mass as shown in Table 3.
[0420] (Comparative Example 6)
[0421] In the production of polymer (X2), the polymerization reaction time was changed to change the weight average molecular weight of polymer (X2) from 500,000 to 1.2 million. Also, the blending amounts of tackifier (TF) and crosslinking agent were changed to the parts by weight shown in Table 3. Other than that, the same procedures as in Example 1 were followed.
[0422] (Comparative Example 7)
[0423] The same procedure as in Example 1 was carried out except that the amount of the crosslinking agent was changed to parts by mass as shown in Table 3.
[0424] Table 3
[0425]
[0426] ※Molecular weight is weight average molecular weight (Mw).
[0427] ※The mass parts of monomers are values when the total amount of monomers blended when synthesizing the polymer (X2) is 100 mass parts. The polymer (X2) can be considered to contain the structural units derived from the monomers listed in Table 1 in the amounts listed in Table 1.
[0428] ※The blending amounts of the tackifier (TF) and the crosslinking agent are parts by mass relative to 100 parts by mass of the polymer (X2).
[0429] [Table 4]
[0430]
[0431] In the above examples, the peak molecular weight (Mtp) of the sol part of the adhesive measured by gel permeation chromatography (GPC) is 137,000 or more and 300,000 or less, the sol fraction (Rsol) of the adhesive is 90% by mass or less, and the glass transition temperature (Tg) of the adhesive is 5°C or less. As a result, the bonding property to the low-polarity adherend (polypropylene resin), the retention force at high temperature, and the low-temperature adhesion are all good. On the other hand, in the comparative examples, the peak molecular weight (Mtp) of the sol part of the adhesive measured by gel permeation chromatography (GPC) deviates from the range of 137,000 or more and 300,000 or less, or the sol fraction (Rsol) of the adhesive is higher than 90% by mass, or the glass transition temperature (Tg) of the adhesive is higher than 5°C. Therefore, it is not possible to improve the biomass rate while making all the bonding property to the low-polarity adherend (polypropylene resin), the retention force at high temperature, and the low-temperature adhesion good.
Claims
1. An adhesive comprising a polymer (X1) containing 48% by mass or more of a structural unit derived from a monomer (Y), wherein the monomer (Y) is at least one selected from a monomer (A1) represented by the following general formula (1) and a monomer (B1) represented by the following general formula (2), When the storage modulus at 23°C is G'(23°C) and the loss modulus at 23°C is G"(23°C), tanδ(23°C) obtained by G"(23°C) / G'(23°C) is 0.8 to 1.
3. In formula (1), R 1 Indicates H or CH3, R 2 Indicates -C n H 2n+1 , n represents an integer from 7 to 14, In formula (2), R 3 Represents -C(=O)C m H 2m+1 , m represents an integer from 6 to 13. 2 . The adhesive according to claim 1 , wherein the weight average molecular weight of the polymer (X1) is 200,000 to 1,000,000.
3. The adhesive according to claim 1 or 2, having a cross-linking degree of 10 to 70%.
4. The adhesive according to any one of claims 1 to 3, wherein logG'(0°C) is 5.0 to 6.5 when the storage modulus at 0°C is G'(0°C), wherein The unit of G'(0℃) is Pa.
5. The adhesive according to any one of claims 1 to 4, wherein logG'(23°C) is 4.8 to 5.5 when the storage modulus at 23°C is G'(23°C), wherein The unit of G'(23°C) is Pa.
6. The adhesive according to any one of claims 1 to 5, wherein logG'(80°C) is 4.1 to 4.8 when the storage modulus at 80°C is G'(80°C), wherein The unit of G'(80℃) is Pa.
7. The adhesive according to any one of claims 1 to 6, having a glass transition temperature (Tg) of 15°C or less.
8. The adhesive according to any one of claims 1 to 7, wherein the content of biogenic carbon is 40% by mass or more. 9 . The adhesive according to claim 1 , further comprising a tackifier. 10 . An adhesive tape comprising an adhesive layer comprising the adhesive according to claim 1 . 11 . The adhesive tape according to claim 10 , further comprising a substrate, wherein the adhesive layer is provided on at least one surface of the substrate. 12 . The adhesive tape according to claim 11 , wherein the substrate is any one selected from the group consisting of nonwoven fabric, polyethylene terephthalate film and foam.
13. A fixing method for fixing a component of an electric product or a vehicle-mounted component using the adhesive according to any one of claims 1 to 9 or the adhesive tape according to any one of claims 10 to 12.
14. An adhesive sheet comprising the adhesive according to any one of claims 1 to 9, The peak top molecular weight (Mtp) of the sol portion of the adhesive measured by gel permeation chromatography (GPC) is greater than or equal to 137,000 and less than or equal to 300,000, The sol fraction (R sol ) is less than 90 mass %, The adhesive has a glass transition temperature (Tg) of 5° C. or less.
15. An adhesive sheet comprising an adhesive containing a biologically derived component, The peak top molecular weight (Mtp) of the sol portion of the adhesive measured by gel permeation chromatography (GPC) is 137,000 or more and 300,000 or less, The sol fraction (R sol ) is less than 90 mass %, The adhesive has a glass transition temperature (Tg) of 5° C. or less.
16. The adhesive sheet according to claim 15, wherein the hardness (S) of the adhesive represented by the following general formula (3) is 50,000 or more and 180,000 or less, S=Mw×R sol / D (3) In formula (3), Mw represents the weight average molecular weight of the sol part of the adhesive measured by GPC, and R sol represents the sol fraction in the adhesive, and D represents the dispersion degree of the sol part of the adhesive measured by GPC. 17 . The adhesive sheet according to claim 15 , wherein the degree of dispersion (D) of the sol portion of the adhesive measured by GPC is 1.6 or more and less than 3. 18 . The adhesive sheet according to claim 15 , wherein the weight average molecular weight (Mw) of the sol portion of the adhesive measured by GPC is 190,000 to 700,000.
19. The adhesive sheet according to any one of claims 15 to 18, wherein the sol fraction (R sol ) is 45 mass % or more and 75 mass % or less. 20 . The adhesive sheet according to claim 15 , wherein the adhesive has a glass transition temperature (Tg) of 2.5° C. or less.
21. The adhesive sheet according to any one of claims 15 to 20, wherein the biomass fraction of the adhesive is 51% or more.
22. The adhesive sheet according to any one of claims 15 to 21, wherein the adhesive comprises a polymer (X2) containing 48% by mass or more of a structural unit derived from a monomer (Y2), wherein the monomer (Y2) is at least one selected from a monomer (A2) represented by the following general formula (4) and a monomer (B2) represented by the following general formula (5), In formula (4), R 4 Indicates H or CH3, R 5 Indicates -C n H 2n+1 , n represents an integer from 7 to 20, In formula (5), R 6 Represents -C(=O)C m H 2m+1 , m represents an integer from 6 to 13. 23 . The adhesive sheet according to claim 22 , wherein the content of the structural unit derived from n-heptyl (meth)acrylate in the polymer (X2) is 48% by mass or more. 24 . An electrical product comprising the adhesive according to claim 1 , the adhesive tape according to claim 10 , or the adhesive sheet according to claim 14 . 25 . A vehicle-mounted component comprising the adhesive according to claim 1 , the adhesive tape according to claim 10 , or the adhesive sheet according to claim 14 .
Citation Information
Patent Citations
Thermally conductive adhesive tape, article and image display device
JP2015021067A
Double-sided adhesive sheet
JP2015120876A